Survey of management practices related to parasite control from ranched North American bison (Bison bison) in the southern United States - Kaylee R. Kipp; Joe L. Luksovsky; Christine M. Budke; Walter E. Cook; John S. Gilleard; Guilherme G. Verocai (Veterinary Parasitology, 2026)

Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Novel spodumene flotation collector development: A comparative review - Amanda Pacholczak; Brian Kawenski Cook; Rachel J. Baker; Charlotte E. Gibson (Minerals Engineering, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Understanding the influence of environmentally persistent free radical location on reactive oxygen species generation in soils - Myron L. Lard; Sarah E. Eichler; Lavrent Khachatryan; Randall Hall; Stephania A. Cormier; Robert L. Cook; Jennifer Richmond-Bryant (Chemosphere, 2026)

Per- and polyfluoroalkyl substances (PFAS) and fish consumption in the Great Lakes Fish Consumer Study (GLFCS) - Meghan Cerpa; Saria Awadalla; Robert M. Sargis; Henry Anderson; Julianne Cook Botelho; Antonia M. Calafat; Victoria Persky; Mary E. Turyk (Chemosphere, 2026)

Genes Versus Environment: Body Size Variation Among Recruitment Cohorts of Dungeness Crab - James L. Dimond; Sarah K. Grossman; Emily V. Buckner; Claire E. Cook; Katelyn M. Bosley; Elizabeth D. Tobin; Julie S. Barber (Molecular Ecology, 2026)
Understanding the drivers of phenotypic variation is key to disentangling the evolutionary and environmental forces that shape patterns of trait variation within and among populations. In Dungeness crab, settlement‐stage megalopae exhibit striking seasonal variation in body size, with early season cohorts consistently larger than later ones. This pattern may result from genetically distinct larval sources or environmentally induced plasticity following the temperature–size rule, which predicts larger body size at cooler temperatures. Here, we evaluated the relative contributions of these potential drivers by analysing megalopae size, regional sea surface temperatures and whole‐genome resequencing data from megalopae collected across the ~5‐month settlement season throughout Washington, USA. Genomic analyses revealed a subtle coastal ancestry signal in early‐arriving megalopae, supporting the hypothesis that these megalopae are of coastal origin. Coastal ancestry was associated with larger megalopae, even after accounting for temperature; however, temperature was a stronger predictor, with a standardised effect size more than three times greater than that of ancestry. A genome‐wide association study found no significant associations with megalopae size, suggesting the absence of a strong genotype–phenotype relationship or a lack of statistical power to detect a highly polygenic trait. Together with prior laboratory rearing studies, our findings support a dominant role for environmentally driven plasticity in body size variation. Persistent cohort differences previously observed in juvenile and adult body size raise the possibility that thermal conditions during early life may promote a carryover effect with potentially significant demographic and fishery implications.

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Longitudinal patterns of urinary biomarkers of placental and renal function in pregnancy and associations with early pregnancy exposure to phthalates and replacements - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Reproductive Toxicology, 2026)

Food Security Outcomes and Postintervention Experiences in a Produce Prescription Pilot: A Mixed-Methods Study - Caroline E. Owens; Miranda Cook; Tammy Reasoner; Aleta McLean; Amy Elsasser; Ciara Long; Amy Webb Girard (Journal of Nutrition Education and Behavior, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Correction: Cutaneous α-Synuclein Pathology as a Differential Marker: A Histological and Statistical Comparison across Neurodegenerative Disease Groups - Dorota Šebelová; Kateřina Menšíková; Michaela Kaiserová; Lenka Satke; Zuzana Grambalová; Kateřina Čížková; Zdeněk Tauber; Kateřina Klíčová; Dominik Hraboš; Sarah E. V. Cook; Jana Zapletalová; Petr Kaňovský (Journal of Molecular Neuroscience, 2026)

When similar chemicals meet different rules: Environmental standards in the licensing of medicinal and plant protection products in the EU and USA - Sophie E. Cook; Martin Scheringer; Eva Lieberherr (Journal of Environmental Management, 2026)

Cognition as a Conservation Tool: A Case Study of Florida Manatees and Boat Strikes - Gordon B. Bauer; Charles J. Deutsch; Roger L. Reep; Wendi Fellner; Tabitha Gunnars; Peter F. Cook; Heidi E. Harley; Athena M. Rycyk (Marine Mammal Science, 2026)
Boat strikes injure and kill large numbers of Florida manatees ( Trichechus manatus latirostris ) each year. Management actions taken to mitigate this threat can be potentially enhanced by consideration of manatee cognitive processes. The role of cognition in marine mammal conservation has received little consideration in the literature. Here, we integrate discoveries from laboratory research on auditory sensory processes and perception with findings from field studies of how manatees respond to motorized vessels and the effect of the ambient soundscape on response times to boat noise. We incorporate that information into recommendations for manatee management to further reduce the risk of collisions. We also suggest lines of research to investigate other relevant cognitive issues—including attention, learning, memory, and decision‐making—to improve conservation efforts and understanding of manatee behavior.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sea lions as a natural model for charting the developmental course following in utero exposure to domoic acid - Peter F. Cook; Colleen Reichmuth; Megan E. Moriarty; Alissa C. Deming; Vanessa Fravel Hoard; Cara Field; Frances Gulland (Harmful Algae, 2026)

Restoring Australia’s Freshwater Wetlands: Rural Landholder Perspectives - Elizabeth P Galanis; Lai Ming Lam; Lukas Schuster; Damien Cook; Martino E Malerba (Wetlands, 2026)
Wetlands are among the most productive and biodiverse ecosystems in the world, yet they are also the most threatened. These vital habitats play a crucial role in mitigating climate change. Although most freshwater wetlands occur on private property, limited research exists on landholder perceptions of their ownership and management. We interviewed landholders who participated in a wetland restoration program. Our interviews explored motivations and barriers to participation and the impact of climate change, if any, on landholders. We conducted a thematic analysis of interview transcripts. Our analysis revealed three major themes. First, participants were motivated by the intrinsic value of nature, focusing on benefits to native flora and fauna rather than personal gain. They expressed strong emotional connections to nature and a sense of stewardship. Second, the removal of bureaucratic, financial and practical barriers by a knowledgeable local facilitator was important for participation. Third, participants acknowledged the tension between agricultural practices and the needs of nature, striving to balance these competing demands. Although climate change was recognised, the primary motivator was restoring natural ecosystems. Restoring freshwater wetlands can help policymakers achieve international and domestic biodiversity goals by aligning conservation programs with landholders’ values. Employing local facilitators with intimate knowledge of the community and ecosystem can enhance program engagement. Additionally, integrating agricultural and environmental needs, such as through agritourism, can further support biodiversity, and the economic and mental resilience of landholders.

Integrating the Microbiome Into Infection Ecology and Evolution in Wild Animals - Jingdi Li; Ian Will; Luís M. Silva; Tommy J. Travers‐Cook; Paradyse E. Blackwood; Kayla C. King (Molecular Ecology, 2026)
Parasites are a ubiquitous force in nature threatening wildlife populations and ecosystems. Interactions between hosts and their parasites are impacted by host‐associated microbiomes, which are essential for host development, physiology and immunity. We synthesise current understanding of the ecological interactions between host microbiomes and parasites, ranging from competitive to facilitative, and explore their potential evolutionary consequences for parasite virulence and transmission in the wild. We highlight recent mechanistic insights that support integrating a microbiome perspective into wildlife parasitology, with examples across diverse animal taxa including amphibians, bats, insects and corals, particularly within the context of climate change. Adopting such a holistic approach can open new avenues whereby host microbial shifts can be used to predict and mitigate infectious diseases in wild populations. Finally, we propose a conceptual framework to guide future research on microbiome‐parasite–host interactions, aiming to better reflect natural ecological complexities and advance both fundamental understanding and conservation applications.

Cutaneous α-Synuclein Pathology as a Differential Marker: A Histological and Statistical Comparison across Neurodegenerative Disease Groups - Dorota Šebelová; Kateřina Menšíková; Michaela Kaiserová; Lenka Satke; Zuzana Grambalová; Kateřina Čížková; Zdeněk Tauber; Kateřina Klíčová; Dominik Hraboš; Sarah E. V. Cook; Jana Zapletalová; Petr Kaňovský (Journal of Molecular Neuroscience, 2026)
There is an urgent need for early and accurate biomarkers of neurodegenerative disorders. Due to the high innervation and accessibility of the skin, a skin biopsy is a minimally invasive method of detecting phosphorylated α-synuclein (p-α-syn) and assessing intraepidermal nerve fiber density (IENFD). We analyzed biopsies taken from the back and the leg of patients with parkinsonian syndromes (Park.sy.), α-synucleinopathies, multiple system atrophies (MSA), tauopathies, and other neurological disorders, as well as from healthy controls. Double immunofluorescence was performed for p-α-syn (Ser129) and protein gene product 9.5 (PGP 9.5), alongside quantitative IENFD assessment. p-α-syn was significantly more prevalent in the patient groups than in the control group. The highest prevalence was observed in patients with parkinsonian syndromes, α-synucleinopathies and MSA. Tauopathies showed preferential paravertebral positivity. Reduction or absence of IENFD was most pronounced in tauopathies (75%), while IENFD was most commonly preserved in MSA (83.3%), indicating that disease-specific patterns of peripheral nerve involvement are exhibited. p-α-syn positivity was found to correlate with shorter disease duration, suggesting its potential as an early biomarker. Combined with olfactory testing, cutaneous markers improved diagnostic discrimination. Our findings support the use of skin biopsies as a promising clinical tool in diagnosing biomarker-based neurodegenerative diseases.

New Zealand blackcurrant extract has no effect on physiological and cardiovascular responses during low-intensity sustained intermittent isometric contractions in men - Stefano Montanari; Ben J. Lee; Sam D. Blacker; Matthew D. Cook; Mark E. T. Willems (European Journal of Applied Physiology, 2026)

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

A submarine mud volcano eruption triggered a 100 m thick mass flow - Muhedeen A. Lawal; Ann E. Cook; Derek E. Sawyer (Marine Geology, 2026)

Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

What temperature is best for the offshore farming of the Australasian snapper, Chrysophrys auratus ? A collective examination of growth, FCR, O 2 consumption and welfare - Selwyn P. Collins; Leonardo J. Magnoni; Denham G. Cook; Suzanne E. Black; Neill A. Herbert (New Zealand Journal of Marine and Freshwater Research, 2025)
The Australasian snapper ( Chrysophrys auratus ) is a candidate for offshore aquaculture in New Zealand. The culture of snapper requires knowledge of the best locations for farms and a key variable is water temperature. The oxygen‐ and capacity‐limited thermal tolerance (OCLTT) hypothesis suggests fish performance is optimised at the temperature that maximises absolute aerobic scope (AAS), whereas the ‘multiple performances–multiple optima’ (MPMO) idea, suggests AAS and other performance measures can have different optimal temperatures. Therefore, the applicability of the OCLTT for snapper was tested by holding juveniles at 15, 18, 21, or 24°C for two months and constructing thermal performance curves (TPCs) for specific growth rate (SGR), feed conversion ratio (FCR) and AAS, and an assessment of welfare indicators. We hypothesised that the OCLTT would apply with all TPCs optimised at 21°C. However, AAS showed no discernible peak with temperature (although lower at 15 than 18°C); SGR and FCR improved non‐linearly with temperature; and welfare indicators varied little with temperature. This lack of aerobic limitation and evidence of MPMO suggests snapper are amenable to culture across a significant temperature range with warmer water likely providing the highest levels of productivity with maintained welfare.

The state and fate of noble metals in bornite and digenite - Samuel A. King; Cristiana L. Ciobanu; Nigel J. Cook; Ashley D. Slattery; Sarah E. Gilbert; J. Richard Kyle; Kathy Ehrig; Jie Yao (Lithos, 2025)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Characteristics of aqueous film forming foam (AFFF) sites impacted with per- and polyfluoroalkyl substances (PFAS): A 37-site study - Poonam R. Kulkarni; Nicolette E. Andrzejczyk; Arun Gavaskar; Abigail Cartwright; David T. Adamson; John Cook; Charles J. Newell (Water Research, 2025)

Guiding Growth: A Nutrition Support Team's Impact on Clinician Confidence - A. Cook; E. Ryder (Journal of the Academy of Nutrition and Dietetics, 2025)

Time since HIV diagnosis is linked to amnestic mild cognitive impairment (MCI) in older adults with HIV - Jason S. DeFelice; Mark K. Britton; Yancheng Li; Eric C. Porges; Gladys E. Ibañez; Charurut Somboonwit; Robert L. Cook; Ronald A. Cohen; Joseph M. Gullett (Journal of NeuroVirology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Four unusual mortality events of seabirds in the Patagonian Sea, 2000–2006: species affected and possible causes - Marcela M. Uhart; Ralph E. T. Vanstreels; Flavio Quintana; Belén Mattera; Nora Montoya; Leonardo Guzman; Hernan Pacheco Valles; Gemita Pizarro; Carolina A. Marull; Luciana Pozzi; Torsten Mörner; Pablo García-Borboroglu; et al. (Polar Biology, 2025)
The Patagonian Sea is a highly productive marine ecosystem and a hotspot for seabird diversity and density in the Southwest Atlantic Ocean. Reports of unusual mortality events are relatively scarce in this region, likely due to under detection and investigation. In this study, we report on four unusual mortality events affecting seabirds in the Patagonian Sea from 2000 to 2006. Events 1 and 2 occurred at Golfo Nuevo and Chubut coast, Argentina in September–December 2000, affecting at least 4550 seabirds, mainly Magellanic penguins ( Spheniscus magellanicus ). Event 3 occurred at the Falkland/Malvinas Islands during December 2002–January 2003, affecting at least 3500 seabirds, mainly gentoo penguins ( Pygoscelis papua ). Event 4 occurred at Punta Loma and Punta León, Argentina, in November 2006, affecting at least 57 seabirds, mainly kelp gulls ( Larus dominicanus ). The aetiology of Events 1 and 2 could not be determined, but malnutrition/starvation and paralytic shellfish poisoning, respectively, were identified as potential causes. Pathological findings and toxicological testing supported paralytic shellfish poisoning as the cause of Events 3 and 4. Our results illustrate how identifying the occurrence, cause and extent of unusual mortality events affecting seabirds can present significant challenges. Moreover, our investigations of the events display variations in timeliness and completeness, and our lack of certainty on aetiology reflects the shortcomings often faced in remote locations and low resource settings. Technological advances, such as smartphones, increased public awareness and connectivity, coupled with more and better equipped protected areas and diagnostic laboratories will likely aid in overcoming difficulties from past decades.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Expanding Monitoring Capacity for Potential Invasive Species in Arctic Canada With Environmental DNA Metabarcoding - Elizabeth Boyse; Melody S. Clark; Ian M. Carr; Alison J. Cook; Philippe Archambault; Jean E. Holloway; Zhewen Luo; Michael Milton; Mathieu Roy; Jackie Dawson; Victoria L. Peck (Global Change Biology, 2025)
To date, environmental conditions have been enough to act as an effective barrier to prevent non‐indigenous species from arriving and establishing in Arctic Canada. However, rapidly changing climatic conditions are creating more suitable habitats for non‐indigenous species to potentially establish and become invasive. Concurrently, shipping traffic in parts of Arctic Canada has increased by over 250% since 1990, providing an effective vector for transporting non‐indigenous species to the region. Arctic Canada has been historically undersampled, so Arctic biota inventories are incomplete, hampering efforts to establish if a species is new to the region (and potentially invasive) or newly discovered. In this study, we utilize environmental DNA (eDNA) metabarcoding and ships of opportunity to assess eukaryotic community composition and potential invasives along one of the busiest shipping routes, the Northwest Passage. One liter seawater samples were collected in triplicate at 27 locations, targeting touristic hotspots frequently visited by passenger vessels. Eukaryotic DNA was amplified from the 18S rRNA V9 and COI regions, resulting in 126 unique Amplicon Sequence Variants (ASVs) detected with COI and 391 ASVs with 18S, providing an important snapshot of current community composition. Copepods, dinoflagellates, and diatoms were the most abundant taxonomic groups, correlating well with previous net sampler surveys, validating the efficacy of eDNA for biodiversity surveillance. We also report the first detections of a prolific invasive species, the bay barnacle ( Amphibalanus improvisus ), in Arctic Canada. Further work is currently in progress to establish whether these detections represent transient barnacle larvae or sessile adults capable of recruiting and reproducing. Our study demonstrates the utility of eDNA for the detection of non‐indigenous species in a data‐poor area, which, if combined with citizen science initiatives and local communities, could provide a vital monitoring tool for the detection of new invasives in this rapidly changing area.

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Exposure to phthalates and replacements during pregnancy in association with gestational blood pressure and hypertensive disorders of pregnancy - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Emma M. Rosen; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Environmental Research, 2025)

Varying climate signals embedded in latewood blue intensity along an elevational gradient: A multi-species case study from the Great Basin, Nevada, USA - Karen E. King; Edward R. Cook; Paul J. Krusic; Daniel J. King (Dendrochronologia, 2025)

Improved Estimates of Biomass Expansion Factors and Root‐To‐Shoot Ratios: An Approach for Different Forest Types Across a Climatic Gradient in Brazil - Isáira Leite e Lopes; Otávio Camargo Campoe; Geovanni Malatesta Barros; Anny Francielly Ataide Gonçalves; Gabriela Gonçalves Moreira Matzner; Marco Aurelio Figura; Clayton Alcarde Alvares; Fernanda Leite Cunha; Verônica Boarini Sampaio de Rezende; James Stahl; Josiana Jussara Nazaré Basílio; Hyngrid Jaiely Araújo Félix; et al. (Global Change Biology, 2025)
Advancements in the current state of the art of the key drivers of biomass expansion factor (BEF) and the root‐to‐shoot ratio ( R ) are crucial for producing accurate information on forest biomass and carbon stocks. Hence, we compiled a nationally representative dataset encompassing diverse tree growth stages and climatic gradients. In this study, we propose models to improve BEF and R estimates at the tree level for Eucalyptus and Pinus plantations in Brazil. In general, the BEF values were more representative (91.7%) in the database than the R values (8.3%) due to the high cost of collecting coarse roots. Regarding genera, Eucalyptus was more extensively sampled (89.9%) than Pinus (10.1%), reflecting the predominance of Eucalyptus as the most widely planted genus in Brazil. The average BEF and R values calculated in this study were 1.16 and 0.22, respectively, for Eucalyptus spp. and 1.22 and 0.31, respectively, for Pinus spp. In predicting the BEFs, the random effects in the linear mixed model that significantly captured the variations in Eucalyptus and Pinus spp. were temperature and age class, respectively. The fixed effects for Eucalyptus spp. included diameter, height, and age, while for Pinus spp., they were the Köppen climate classification, species, slenderness degree, and age. R estimates were mainly influenced by precipitation and age for both genera, with slenderness and diameter specifically affecting Eucalyptus spp., and height being a driving factor for Pinus spp. Our findings discourage the use of fixed or default values for BEF and R across locations with different climates and growing conditions to reduce uncertainties in carbon accounting and greenhouse gas inventories.

Vertebral elemental composition reveals ontogenetic changes in habitat use in a Northeast Atlantic mesopredator shark - Neil D. Cook; Ana Samperiz; Morten Andersen; Edward Inglis; Marc-Alban Millet; Jo Cable; Sarah E. Perkins (Estuarine, Coastal and Shelf Science, 2025)

Framework for assessing species vulnerability whilst on migration to a spatially explicit anthropogenic pressure - Ros M.W. Green; Niall H.K. Burton; Aonghais S.C.P. Cook; Samantha E. Franks; Jonathan A. Green (Biological Conservation, 2025)

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Gas hydrate in the Faroe-Shetland Basin, offshore United Kingdom - Fawz Naim; Ann E. Cook (Marine and Petroleum Geology, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

STICr: An open-source package and workflow for stream temperature, intermittency, and conductivity (STIC) data - Sam Zipper; Christopher T. Wheeler; Delaney M. Peterson; Stephen C. Cook; Sarah E. Godsey; Ken Aho (Environmental Modelling & Software, 2025)

Ecosystem Services Provided by Seaweed Cultivation: State of the Art, Knowledge Gaps, Constraints and Future Needs for Achieving Maximum Potential in Europe - Fricke A; Capuzzo E; Bermejo R; Hofmann LC; Hernández I; Pereira R; Van den Burg SWK; Pereira T; Buschmann AH; Cottier-Cook EJ (Reviews in Fisheries Science & Aquaculture, 2025)

Catalytic consequences of catalyst pellet architecture on the direct production of dimethoxymethane from methanol. - Sebastian M.K. Cook; William Thomas Broomhead; Adam Johnston; Ya-Huei Cathy Chin; José E. Herrera (Chemical Engineering Journal, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

New opportunities and challenges for conservation evidence synthesis from advances in natural language processing - Charlotte H. Chang; Susan C. Cook‐Patton; James T. Erbaugh; Luci Lu; Yuta J. Masuda; István Molnár; Dávid Papp; Brian E. Robinson (Conservation Biology, 2025)
Addressing global environmental conservation problems requires rapidly translating natural and conservation social science evidence to policy‐relevant information. Yet, exponential increases in scientific production combined with disciplinary differences in reporting research make interdisciplinary evidence syntheses especially challenging. Ongoing developments in natural language processing (NLP), such as large language models, machine learning (ML), and data mining, hold the promise of accelerating cross‐disciplinary evidence syntheses and primary research. The evolution of ML, NLP, and artificial intelligence (AI) systems in computational science research provides new approaches to accelerate all stages of evidence synthesis in conservation social science. To show how ML, language processing, and AI can help automate and scale evidence syntheses in conservation social science, we describe methods that can automate querying the literature, process large and unstructured bodies of textual evidence, and extract parameters of interest from scientific studies. Automation can translate to other research agendas in conservation social science by categorizing and labeling data at scale, yet there are major unanswered questions about how to use hybrid AI‐expert systems ethically and effectively in conservation.

Gas migration phenomena and pockmark evolution in a Gulf of Mexico minibasin - Muhedeen A. Lawal; Ann E. Cook (Marine and Petroleum Geology, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Associations between per- and polyfluoroalkyl substances (PFAS) and female sexual function in a preconception cohort - Samantha Schildroth; Julia C. Bond; Amelia K. Wesselink; Jasmine Abrams; Antonia M. Calafat; Julianne Cook Botelho; Katharine O. White; Ganesa Wegienka; Elizabeth E. Hatch; Lauren A. Wise (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

A tiered assessment of human health risks associated with exposure to persistent, mobile and toxic chemicals via drinking water - M.J. Whelan; E. Pemberton; C.B. Hughes; C. Swansborough; E.H. Goslan; T. Gouin; V.A. Bell; E. Bird; S. Bull; L. Segal; S.H. Cook; C. Jephcote; et al. (Science of The Total Environment, 2025)

A quantitative approach to ranking management actions for an endangered pool-breeding amphibian - Aidan E. O'Brien; David G. Cook; Stacy Martinelli; Michael H. Fawcett; Christopher A. Searcy (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Modeling growth of multiple recruitment cohorts of Dungeness crab co-occurring within the central Salish Sea - Claire E. Cook; Sarah K. Grossman; Julie S. Barber (Journal of Experimental Marine Biology and Ecology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Temporal niche partitioning as a potential mechanism for coexistence in two sympatric mesopredator sharks - Neil D. Cook; Abbie Jenkins; Sarah L. Perry; Sarah E. Perkins; Jo Cable (Frontiers in Marine Science, 2024)
Global marine biodiversity declines require bold and ambitious plans to safeguard ecosystem services. Overfishing, habitat loss and projected climate impacts have yielded deleterious effects on marine predators, in particular, driving increasing threat of extinction for many shark species with implications for ecosystem health. Identifying and protecting critical habitat areas for sharks is fundamental to their protection, and may allow for species recovery. Here we use baited remote underwater video stations to investigate spatial and temporal patterns of habitat use by sharks in a Special Area of Conservation (SAC) that is centrally important to the regional blue economy in the UK, the Cardigan Bay SAC. Our results show heterogeneous spatial habitat use and temporal trends in habitat sharing between smallspotted catsharks Scyliorhinus canicula and nursehounds S. stellaris . Nearshore reef habitats are substantially more important than non-reef habitats for both species. The relative abundance of each species, however, is roughly inversely seasonally proportional, with S. canicula and S. stellaris relative abundance highest in March and September, respectively. Temporal niche partitioning may be an important mechanism in marine systems, but has not been widely investigated in sympatric shark communities. These findings are directly relevant for ongoing development of the Welsh Marine Evidence Strategy (2019-2025) and the Welsh National Marine Plan, particularly to inform spatial planning to strengthen the role of SAC management design in protecting important shark areas.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

Bottom simulating reflections across the northern Gulf of Mexico slope - Aditya Kumar; Ann E. Cook; Alexey Portnov; Stuart Skopec; Matthew Frye; Stephen Palmes (Marine and Petroleum Geology, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

An analysis of culture-based methods used for the detection and isolation of Salmonella spp., Escherichia coli, and Enterococcus spp. from surface water: A systematic review - Betty R. McConn; Autumn L. Kraft; Lisa M. Durso; Abasiofiok M. Ibekwe; Jonathan G. Frye; James E. Wells; Elizabeth M. Tobey; Stephanie Ritchie; Clinton F. Williams; Kimberly L. Cook; Manan Sharma (Science of The Total Environment, 2024)

Gas hydrate in the North Carnarvon Basin, offshore Western Australia - Fawz Naim; Ann E. Cook (Marine and Petroleum Geology, 2024)

Well-established populations of the western drywood termite, Incisitermes minor (Blattodea: Kalotermitidae), in Korea - Sang-Bin Lee; Sunghyuk Jeong; Hyobin Lee; Yejin Kang; Suseong Lee; Na Ra Jeong; Jaehyeon Lee; Sanghyo Park; Jaewon Kim; Inhyeok Han; Hyeongsu Kim; Jaeyun Kim; et al. (Journal of Asia-Pacific Entomology, 2024)

Trace element impurities in anode copper from Olympic Dam, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Sarah E. Gilbert; Hassan Gezzaz (Minerals Engineering, 2024)

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

A tale of 3 dwarf planets: Ices and organics on Sedna, Gonggong, and Quaoar from JWST spectroscopy - J.P. Emery; I. Wong; R. Brunetto; J.C. Cook; N. Pinilla-Alonso; J.A. Stansberry; B.J. Holler; W.M. Grundy; S. Protopapa; A.C. Souza-Feliciano; E. Fernández-Valenzuela; J.I. Lunine; et al. (Icarus, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Spontaneous Behavioural Recovery Following Stroke Relates to the Integrity of Parietal and Temporal Regions - Joseph Y. Nashed; Kaden T. Shearer; Justin Z. Wang; Yining Chen; Elise E. Cook; Allen A. Champagne; Nicole S. Coverdale; Juan Fernandez-Ruiz; Shirley I. Striver; J. Randal Flanagan; Jason P. Gallivan; Douglas J. Cook (Translational Stroke Research, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Horizon scanning of potential threats to high‐Arctic biodiversity, human health and the economy from marine invasive alien species: A Svalbard case study - Elizabeth J. Cottier‐Cook; Jude Bentley‐Abbot; Finlo R. Cottier; Dan Minchin; Sergej Olenin; Paul E. Renaud (Global Change Biology, 2024)
The high Arctic is considered a pristine environment compared with many other regions in the northern hemisphere. It is becoming increasingly vulnerable to invasion by invasive alien species (IAS), however, as climate change leads to rapid loss of sea ice, changes in ocean temperature and salinity, and enhanced human activities. These changes are likely to increase the incidence of arrival and the potential for establishment of IAS in the region. To predict the impact of IAS, a group of experts in taxonomy, invasion biology and Arctic ecology carried out a horizon scanning exercise using the Svalbard archipelago as a case study, to identify the species that present the highest risk to biodiversity, human health and the economy within the next 10 years. A total of 114 species, currently absent from Svalbard, recorded once and/or identified only from environmental DNA samples, were initially identified as relevant for review. Seven species were found to present a high invasion risk and to potentially cause a significant negative impact on biodiversity and five species had the potential to have an economic impact on Svalbard. Decapod crabs, ascidians and barnacles dominated the list of highest risk marine IAS. Potential pathways of invasion were also researched, the most common were found associated with vessel traffic. We recommend (i) use of this approach as a key tool within the application of biosecurity measures in the wider high Arctic, (ii) the addition of this tool to early warning systems for strengthening existing surveillance measures; and (iii) that this approach is used to identify high‐risk terrestrial and freshwater IAS to understand the overall threat facing the high Arctic. Without the application of biosecurity measures, including horizon scanning, there is a greater risk that marine IAS invasions will increase, leading to unforeseen changes in the environment and economy of the high Arctic.

A comparison of methods to detect low levels of Salmonella enterica in surface waters to support antimicrobial resistance surveillance efforts performed in multiple laboratories - Autumn L. Kraft; Jim E. Wells; Jonathan G. Frye; Abasiofiok M. Ibekwe; Lisa M. Durso; Lari Hiott; Cheryl East; Betty R. McConn; Alison M. Franklin; Laura A. Boczek; Jay L. Garland; Claudine Kabera; et al. (Science of The Total Environment, 2023)

Optimization of spodumene flotation with a fatty acid collector - Brian Kawenski Cook; Massoud Aghamirian; Charlotte E. Gibson (Minerals Engineering, 2023)

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Global variability and controls on the accumulation of fallout radionuclides in cryoconite - Caroline C. Clason; Giovanni Baccolo; Edyta Łokas; Philip N. Owens; Przemyslaw Wachniew; Geoff E. Millward; Alex Taylor; Will H. Blake; Dylan B. Beard; Ewa Poniecka; Nick Selmes; Elizabeth A. Bagshaw; et al. (Science of The Total Environment, 2023)

Heat stress survival and thermal tolerance of Australian stingless bees - Scott Nacko; Mark A. Hall; Rosalyn Gloag; Kate E. Lynch; Robert N. Spooner-Hart; James M. Cook; Markus Riegler (Journal of Thermal Biology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Seeing the wood for the trees, irregular silviculture supports bat populations in conifer plantations - Patrick Cook; Daniel Alder; Lisbeth Hordley; Stuart E. Newson; David Pengelly (Forest Ecology and Management, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Ground-based remote sensing provides alternative to satellites for monitoring cyanobacteria in small lakes - Katherine V. Cook; Jessica E. Beyer; Xiangming Xiao; K. David Hambright (Water Research, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

Microbial diversity in stingless bee gut is linked to host wing size and influenced by the environment - Hongwei Liu; Mark A. Hall; Laura E. Brettell; Juntao Wang; Megan Halcroft; Scott Nacko; Robert Spooner-Hart; James M. Cook; Markus Riegler; Brajesh K. Singh (Journal of Invertebrate Pathology, 2023)

Dynamic Genomes - Mechanisms and consequences of genomic diversity impacting plant-fungal interactions - Jun Huang; Sanzhen Liu; David E. Cook (Physiological and Molecular Plant Pathology, 2023)

A numerical investigation of the mechanisms controlling salt intrusion in the Delaware Bay estuary - Salme E. Cook; John C. Warner; Kendra L. Russell (Estuarine, Coastal and Shelf Science, 2023)

Investigating slow-moving shallow soil landslides using Sentinel-1 InSAR data in Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley (Landslides, 2023)
Landslides are widespread geomorphological features on the North Island of New Zealand, where they represent one of the primary landscape-forming processes. This study focuses on the steepland terrain surrounding Gisborne, a city located on the east coast of the North Island, at the Hikurangi subduction margin. This terrain consists of young, weak, sedimentary rocks and soils; the most common modes of slope failures are soil creep, slides and flows in shallow, clay-rich soil and regolith, triggered by heavy rainfall. Based on observational data from Sentinel-1 imagery, this study leverages results from interferometric synthetic aperture radar (InSAR) processing to reveal the distribution of deformation across Gisborne’s steepland periphery from January 2016 to December 2021. Velocities in the line of sight were obtained from the stack of interferograms and projected along the direction of maximum slope, to extract the true displacement on the slopes. The ascending and descending data sets were combined to reveal the vertical and horizontal components of the deformation. The results were combined with a regional LiDAR data set, aerial imagery and field observations to delineate areas of slope deformation. Finally, slope deformation time series data was compared with rainfall records to identify seasonal changes, due to shrinking and swelling of expansive soils. Although the InSAR displacement data contains some noise, results could be used to identify 132 unstable slopes within the study area, caused by soil creep and earthflows. Also, the shrink-swell of expansive soils causes a seasonal pattern of displacements, which varied by 10–20 mm/year between Austral winter and summer, strongly correlated to rainfall.

Promoting women’s leadership under environmental decentralization: The roles of domestic policy, foreign aid, and population change - Nathan J. Cook; Michelle E. Benedum; Ganesh Gorti; Sitashma Thapa (Environmental Science & Policy, 2023)

Effect of biosecurity practices and diseases on growth and carrageenan properties of Kappaphycus alvarezii and Eucheuma denticulatum cultivated in Zanzibar, Tanzania - Msafiri A. Ndawala; Flower E. Msuya; Jennefe P. Cabarubias; Cicilia S. B. Kambey; Amelia S. Buriyo; Esther F. Mvungi; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2022)

Engineering geomorphological and InSAR investigation of an urban landslide, Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley; David J. Alama (Landslides, 2022)
The East Coast region of New Zealand has some of the highest erosion rates in the world, due to its proximity to an active plate boundary, susceptibility to high-intensity storms and steep terrain underlain by young soft sedimentary rock and soil. In the city of Gisborne, expansion of residential blocks into steeper terrain in peri-urban areas has required improved capacity for the characterisation and monitoring of slope stability. Landslides have affected several properties and have destroyed infrastructure. Slope failure commonly occurs during heavy rainfall events when slow-moving retrogressive slides transition into earthflows and mudflows. In this study, we used in situ sampling and testing methods combined with remote sensing techniques to provide an understanding of the pre-failure and post-failure behaviour of an urban landslide in Gisborne. High-resolution aerial imagery, unmanned aerial vehicle imagery and light detection and ranging data revealed slope morphology and contours of prehistoric failures in the area, and highlighted the more recent impacts of deforestation on slope stability. Furthermore, Sentinel-1 InSAR analysis determined that gradual deformation began in 2017, following two ex-tropical cyclone events. Deformation downslope continued until an initial failure in July 2020. Following that event, some parts of the slope proceeded to accelerate, leading to a further reactivation event in November 2021, following heavy rainfall. During this November 2021 event, average line of sight velocities ranged from −7.9 to −11.2 mm/year, and deformation rates in the vertical direction (related to rotational slumping) averaged −11.2 to −11.9 mm/year, consistent with field observations.

Chemistry Manufacturing and Controls Development, Industry Reflections on Manufacture, and Supply of Pandemic Therapies and Vaccines - Matthew E. Popkin; Markus Goese; Diane Wilkinson; Stuart Finnie; Talia Flanagan; Cristiana Campa; Alexandra Clinch; Andrew Teasdale; Andrew Lennard; Graham Cook; Ganapathy Mohan; Matthew D. Osborne (The AAPS Journal, 2022)

Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Holly E. Jenkins; Florence Atherden; Kathryn B. Cook; Thomas R. Anderson; Barry Thornton; Elaine Mitchell; Elodie Jacob; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus , with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day -1 (mean = 0.295 ± 0.223 day -1 ), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day -1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Prostate cancer addiction to oxidative stress defines sensitivity to anti-tumor neutrophils - Diane L. Costanzo-Garvey; Adam J. Case; Gabrielle F. Watson; Massar Alsamraae; Arpita Chatterjee; Rebecca E. Oberley-Deegan; Samikshan Dutta; Maher Y. Abdalla; Tammy Kielian; Merry L. Lindsey; Leah M. Cook (Clinical & Experimental Metastasis, 2022)
Bone metastatic prostate cancer (BM-PCa) remains one of the most difficult cancers to treat due to the complex interactions of cancer and stromal cells. We previously showed that bone marrow neutrophils elicit an anti-tumor immune response against BM-PCa. Further, we demonstrated that BM-PCa induces neutrophil oxidative burst, which has previously been identified to promote primary tumor growth of other cancers, and a goal of this study was to define the importance of neutrophil oxidative burst in BM-PCa. To do this, we first examined the impact of depletion of reactive oxygen species (ROS), via systemic deletion of the main source of ROS in phagocytes, NADPH oxidase (Nox)2, which we found to suppress prostate tumor growth in bone. Further, using pharmacologic ROS inhibitors and Nox2-null neutrophils, we found that ROS depletion specifically suppresses growth of androgen-insensitive prostate cancer cells. Upon closer examination using bulk RNA sequencing analysis, we identified that metastatic prostate cancer induces neutrophil transcriptomic changes that activates pathways associated with response to oxidative stress. In tandem, prostate cancer cells resist neutrophil anti-tumor response via extracellular (i.e., regulation of neutrophils) and intracellular alterations of glutathione synthesis, the most potent cellular antioxidant. These findings demonstrate that BM-PCa thrive under oxidative stress conditions and such that regulation of ROS and glutathione programming could be leveraged for targeting of BM-PCa progression.

The physiological basis underlying functional connectivity differences in older adults: A multi-modal analysis of resting-state fMRI - Allen A. Champagne; Nicole S. Coverdale; Matti D. Allen; Joshua C. Tremblay; Rebecca E. K. MacPherson; Kyra E. Pyke; T. Dylan Olver; Douglas J. Cook (Brain Imaging and Behavior, 2022)

Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Penelope K. Lindeque; Isabelle Hann; Helen E. Parry; Kathryn B. Cook; Anthony J. W. Lindley; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis , accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus- dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Seaweed farming in Africa: current status and future potential - Flower E. Msuya; John Bolton; Fred Pascal; Koushul Narrain; Betty Nyonje; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2022)
Global demand for seaweed and its products has increased exponentially over the last 25 years. Equally, the continent of Africa and its offshore islands have considerable potential for seaweed production to contribute to world demand. Compared with China and the rest of Asia, Africa lags behind in seaweed production and utilisation. However, for red eucheumatoid seaweeds, Africa is the third-largest producer in the world, producing about 120,000 t (FW) annually. Details are provided for 13 African countries that are currently involved in seaweed farming and harvesting, commercially or experimentally, for export or domestic utilisation. Eucheuma spp . and Kappaphycus spp . in Tanzania represent 92% and in Madagascar 4.7% of continental production, and Ulva spp . and Gracilaria spp . in South Africa represent 1.5%. Over 2000 species of seaweed have been recorded in Africa, some of which are already successfully cultivated in other parts of the world. The environmental conditions across the continent range from warm, tropical waters to the cooler, nutrient-rich waters of the southwest, enabling the cultivation of seaweeds from the tropical, carrageenan-producing eucheumatoids to temperate kelp species. Seaweed aquaculture production in Africa, led predominantly by women, has improved the livelihoods of its coastal people. Challenges through disease and pest outbreaks, as a result of climate change, and the low prices paid to farmers are highlighted as major constraints on the development of this industry. Through scaling up and expanding current efforts in production and utilisation of seaweeds, Africa has the potential to join China and Southeast Asia as a global leader in producing, processing and consuming a wide variety of seaweeds.

Local adaptation and spatiotemporal patterns of genetic diversity revealed by repeated sampling of Caenorhabditis elegans across the Hawaiian Islands - Timothy A. Crombie; Paul Battlay; Robyn E. Tanny; Kathryn S. Evans; Claire M. Buchanan; Daniel E. Cook; Clayton M. Dilks; Loraina A. Stinson; Stefan Zdraljevic; Gaotian Zhang; Nicole M. Roberto; Daehan Lee; et al. (Molecular Ecology, 2022)
The nematode Caenorhabditis elegans is among the most widely studied organisms, but relatively little is known about its natural ecology. Genetic diversity is low across much of the globe but high in the Hawaiian Islands and across the Pacific Rim. To characterize the niche and genetic diversity of C. elegans on the Hawaiian Islands and to explore how genetic diversity might be influenced by local adaptation, we repeatedly sampled nematodes over a three‐year period, measured various environmental parameters at each sampling site, and whole‐genome sequenced the C. elegans isolates that we identified. We found that the typical Hawaiian C. elegans niche comprises moderately moist native forests at high elevations (500–1,500 m) where ambient air temperatures are cool (15–20°C). Compared to other Caenorhabditis species found on the Hawaiian Islands ( e.g ., Caenorhabditis briggsae and Caenorhabditis tropicalis ), we found that C. elegans were enriched in native habitats. We measured levels of genetic diversity and differentiation among Hawaiian C. elegans and found evidence of seven genetically distinct groups distributed across the islands. Then, we scanned these genomes for signatures of local adaptation and identified 18 distinct regions that overlap with hyper‐divergent regions, which may be maintained by balancing selection and are enriched for genes related to environmental sensing, xenobiotic detoxification, and pathogen resistance. These results provide strong evidence of local adaptation among Hawaiian C. elegans and contribute to our understanding of the forces that shape genetic diversity on the most remote volcanic archipelago in the world.

Changing hydroclimate dynamics and the 19th to 20th century wetting trend in the English Channel region of northwest Europe - Serena R. Scholz; Richard Seager; Mingfang Ting; Yochanan Kushnir; Jason E. Smerdon; Benjamin I. Cook; Edward R. Cook; Seung Hun Baek (Climate Dynamics, 2022)

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Prioritization and thresholds for managing biological invasions in urban ecosystems - L. J. Potgieter; M. F. J. Aronson; A. J. Brandt; C. N. Cook; M. Gaertner; N. E. Mandrak; D. M. Richardson; N. Shrestha; M. W. Cadotte (Urban Ecosystems, 2022)

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Effects of methylphenidate on reinforcement learning depend on working memory capacity - Mojtaba Rostami Kandroodi; Jennifer L. Cook; Jennifer C. Swart; Monja I. Froböse; Dirk E. M. Geurts; Abdol-Hossein Vahabie; Majid Nili Ahmadabadi; Roshan Cools; Hanneke E. M. den Ouden (Psychopharmacology, 2021)
Rationale Brain catecholamines have long been implicated in reinforcement learning, exemplified by catecholamine drug and genetic effects on probabilistic reversal learning. However, the mechanisms underlying such effects are unclear. Objectives and methods Here we investigated effects of an acute catecholamine challenge with methylphenidate (20 mg, oral) on a novel probabilistic reversal learning paradigm in a within-subject, double-blind randomised design. The paradigm was designed to disentangle effects on punishment avoidance from effects on reward perseveration. Given the known large individual variability in methylphenidate’s effects, we stratified our effects by working memory capacity and trait impulsivity, putatively modulating the effects of methylphenidate, in a large sample ( n = 102) of healthy volunteers. Results Contrary to our prediction, methylphenidate did not alter performance in the reversal phase of the task. Our key finding is that methylphenidate altered learning of choice-outcome contingencies in a manner that depended on individual variability in working memory span. Specifically, methylphenidate improved performance by adaptively reducing the effective learning rate in participants with higher working memory capacity. Conclusions This finding emphasises the important role of working memory in reinforcement learning, as reported in influential recent computational modelling and behavioural work, and highlights the dependence of this interplay on catecholaminergic function.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

Trace Element Patterns in Otoliths: The Role of Biomineralization - Karin Hüssy; Karin E. Limburg; Hélène de Pontual; Oliver R. B. Thomas; Philip K. Cook; Yvette Heimbrand; Martina Blass; Anna M. Sturrock (Reviews in Fisheries Science & Aquaculture, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Assessing the current state of ecological connectivity in a large marine protected area system - Kelsey E. Roberts; Carly N. Cook; Jutta Beher; Eric A. Treml (Conservation Biology, 2021)
The establishment of marine protected areas (MPAs) is a critical step in ensuring the continued persistence of marine biodiversity. Although the area protected in MPAs is growing, the movement of individuals (or larvae) among MPAs, termed connectivity, has only recently been included as an objective of many MPAs. As such, assessing connectivity is often neglected or oversimplified in the planning process. For promoting population persistence, it is important to ensure that protected areas in a system are functionally connected through dispersal or adult movement. We devised a multi‐species model of larval dispersal for the Australian marine environment to evaluate how much local scale connectivity is protected in MPAs and determine whether the extensive system of MPAs truly functions as a network. We focused on non‐migratory species with simplified larval behaviors (i.e., passive larval dispersal) (e.g., no explicit vertical migration) as an illustration. Of all the MPAs analyzed (approximately 2.7 million km 2 ), outside the Great Barrier Reef and Ningaloo Reef,

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

Biosecurity policy and legislation of the seaweed aquaculture industry in Tanzania - Sadock B. Rusekwa; Iona Campbell; Flower E. Msuya; Amelia S. Buriyo; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Pest and disease outbreaks have significant impacts on the livelihoods of seaweed farmers each year, particularly in low- to middle-income countries around the world. Commercial seaweed farming of the red carrageenophytes, Eucheuma denticulatum , Kappaphycus alvarezii and Kappaphycus striatus , in Tanzania was established in 1989. The impacts of pests and diseases on the local seaweed industry had serious implications for the environment, society, local culture and human health. The industry was initially characterised by growth, but since 2002 has been severely limited due to pest and disease outbreaks, exacerbated by the effects of climate change. This paper identifies existing biosecurity frameworks in Tanzanian legislation and policies in order to assess their content regarding the management of pests and diseases in the seaweed industry. A total of thirteen frameworks were identified and analysed for their general biosecurity scope and inclusion of specific risks. Of the thirteen, only four were legally binding, and only four were identified to be applicable to the seaweed industry. National frameworks were predominantly designed to support finfish aquaculture; therefore, national authorities lack the expertise, experience and scientific basis on biosecurity issues in seaweed industry compared with other aquatic commercial commodities to identify and mitigate the risks from pest and disease outbreaks in the seaweed farming industry. Recommendations are provided to assist regulators in establishing biosecurity policies, which either explicitly include or are specifically designed, to support the Tanzanian seaweed industry. This analysis reveals where biosecurity capacity can be developed to support a sustainable and economically productive national seaweed farming industry.

Seasonality of biological and physical systems as indicators of climatic variation and change - Jake F. Weltzin; Julio L. Betancourt; Benjamin I. Cook; Theresa M. Crimmins; Carolyn A. F. Enquist; Michael D. Gerst; John E. Gross; Geoffrey M. Henebry; Rebecca A. Hufft; Melissa A. Kenney; John S. Kimball; Bradley C. Reed; et al. (Climatic Change, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

Biosecurity policy and legislation for the global seaweed aquaculture industry - Iona Campbell; Cicilia S. B. Kambey; Jonalyn P. Mateo; Sadock B. Rusekwa; Anicia Q. Hurtado; Flower E. Msuya; Grant D. Stentiford; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Each year a significant proportion of global food production is lost to pests and diseases, with concerted efforts by government and industry focussed on application of effective biosecurity policies which attempt to minimise their emergence and spread. In aquaculture the volume of seaweeds produced is second only to farmed fish and red algal carrageenophytes currently represent approximately 42% of global production of all seaweeds. Despite this importance, expansion of the seaweed sector is increasingly limited by the high prevalence of recalcitrant diseases and epiphytic pests with potential to emerge and with the demonstrated propensity to spread, particularly in the absence of effective national and international biosecurity policies. Developing biosecurity policy and legislation to manage biosecurity risk in seaweed aquaculture is urgently required to limit these impacts. To understand current international biosecurity frameworks and their efficacy, existing legislative frameworks were analysed quantitatively for the content of biosecurity measures, applicability to the seaweed industry, and inclusion of risks posed by diseases, pests and non-native species. Deficiencies in existing frameworks included the following: inconsistent terminology for inclusion of cultivated seaweeds, unclear designation of implementation responsibility, insufficient evidence-based information and limited alignment of biosecurity hazards and risks. Given the global importance of the cultivation of various seaweeds in alleviating poverty in low and middle income countries, it is crucial that the relatively low-unit value of the industry (i.e. as compared with other aquatic animal sectors) should not conflate with a perceived low risk of disease or pest transfer, nor the subsequent economic and environmental impact that disease transfer may impact on receiving nations (well beyond their seaweed operations). Developing a clear basis for development of robust international biosecurity policies related to the trade in seaweeds arising from the global aquaculture industry, by first addressing the gaps highlighted in this study, will be crucial in limiting impacts of pests and diseases on this valuable industry and on natural capital in locations where seaweeds are farmed.

No statistical support for wolf control and maternal penning as conservation measures for endangered mountain caribou - Lee E. Harding; Mathieu Bourbonnais; Andrew T. Cook; Toby Spribille; Viktoria Wagner; Chris Darimont (Biodiversity and Conservation, 2020)
Mountain caribou, a behaviourally and genetically distinct set of ecotypes of the Woodland caribou ( Rangifer tarandus caribou ) restricted to the mountains of western Canada, have undergone severe population declines in recent decades. Although a broad consensus exists that the ultimate driver of these declines has been the reduction of habitat upon which mountain caribou depend, research and policy attention has increasingly focused on predation. Recently, Serrouya et al. (Proc Nat Acad Sci USA 116:6181–6186, 2019) analysed population dynamics data from 18 subpopulations in British Columbia and Alberta, Canada, subject to different treatments and ‘controls’, and concluded that lethal wolf control and maternal caribou penning provide the most effective ways to stabilize population declines. Here we show that this inference was based on an unbalanced analytical approach that omitted a null scenario, excluded potentially confounding variables and employed irreproducible habitat alteration metrics. Our reanalysis of available data shows that ecotype identity is a better predictor of population trends than any adaptive management treatments considered by Serrouya et al. Disparate behavioural characteristics and responses to industrial disturbance among ecotypes suggest it may be incorrect to assume that adaptive management strategies that might benefit one ecotype are transferable to another.

Simulating alternative sustainable water futures - D. A. Sampson; E. M. Cook; M. J. Davidson; N. B. Grimm; D. M. Iwaniec (Sustainability Science, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Right place. Right time. Right tool: guidance for using target analysis to increase the likelihood of invasive species detection - Jeffrey T. Morisette; Jamie K. Reaser; Gericke L. Cook; Kathryn M. Irvine; Helen E. Roy (Biological Invasions, 2020)
In response to the National Invasive Species Council’s 2016–2018 Management Plan , this paper provides guidance on applying target analysis as part of a comprehensive framework for the early detection of and rapid response to invasive species (EDRR). Target analysis is a strategic approach for detecting one or more invasive species at a specific locality and time, using a particular method and/or technology(ies). Target analyses, which are employed across a wide range of disciplines, are intended to increase the likelihood of detection of a known target in order to maximize survey effectiveness and cost-efficiency. Although target analyses are not yet a standard approach to invasive species management, some federal agencies are employing target analyses in principle and/or in part to improve EDRR capacities. These initiatives can provide a foundation for a more standardized and comprehensive approach to target analyses. Guidance is provided for improving computational information. Federal agencies and their partners would benefit from a concerted effort to collect the information necessary to perform rigorous target analyses and make it available through open access platforms.

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Protected area downgrading, downsizing, and degazettement as a threat to iconic protected areas - Siyu Qin; Rachel E. Golden Kroner; Carly Cook; Anteneh T. Tesfaw; Rowan Braybrook; Carlos Manuel Rodriguez; Claire Poelking; Michael B. Mascia (Conservation Biology, 2019)
Protected areas (PAs) are expected to conserve nature and provide ecosystem services in perpetuity, yet widespread protected area downgrading, downsizing, and degazettement (PADDD) may compromise these objectives. Even iconic protected areas are vulnerable to PADDD, although these PADDD events are often unrecognized. We identified 23 enacted and proposed PADDD events within World Natural Heritage Sites and examined the history, context, and consequences of PADDD events in 4 iconic PAs (Yosemite National Park, Arabian Oryx Sanctuary, Yasuní National Park, and Virunga National Park). Based on insights from published research and international workshops, these 4 cases revealed the diverse pressures brought on by competing interests to develop or exploit natural landscapes and the variety of mechanisms that enables PADDD. Knowledge gaps exist in understanding of the conditions through which development pressures translate to PADDD events and their impacts, partially due to a lack of comprehensive PADDD records. Future research priorities should include comprehensive regional and country‐level profiles and analysis of risks, impacts, and contextual factors related to PADDD. Policy options to better govern PADDD include improving tracking and reporting of PADDD events, establishing transparent PADDD policy processes, coordinating among legal frameworks, and mitigating negative impacts of PADDD. To support PADDD research and policy reforms, enhanced human and financial capacities are needed to train local researchers and to host publicly accessible data. As the conservation community considers the achievements of Aichi Target 11 and moves toward new biodiversity targets beyond 2020, researchers, practitioners, and policy makers need to work together to better track, assess, and govern PADDD globally.

Spiraling Down Hillslopes: Nutrient Uptake from Water Tracks in a Warming Arctic - Tamara K. Harms; Christopher L. Cook; Adam N. Wlostowski; Michael N. Gooseff; Sarah E. Godsey (Ecosystems, 2019)

Climate Change Vulnerability of American Lobster Fishing Communities in Atlantic Canada - Blair J. W. Greenan; Nancy L. Shackell; Kiyomi Ferguson; Philip Greyson; Andrew Cogswell; David Brickman; Zeliang Wang; Adam Cook; Catherine E. Brennan; Vincent S. Saba (Frontiers in Marine Science, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Analysis of recombinant inbred line populations derived from wheat landraces to identify new genes for wheat stem sawfly resistance - Andrea C. Varella; David K. Weaver; Nancy K. Blake; Megan L. Hofland; Hwa-Young Heo; Jason P. Cook; Peggy F. Lamb; Katherine W. Jordan; Eduard Akhunov; Shiaoman Chao; Luther E. Talbert (Theoretical and Applied Genetics, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

A Euro-Mediterranean tree-ring reconstruction of the winter NAO index since 910 C.E. - Edward R. Cook; Yochanan Kushnir; Jason E. Smerdon; A. Park Williams; Kevin J. Anchukaitis; Eugene R. Wahl (Climate Dynamics, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Forest Fertilizer Applications in the Southeastern United States from 1969 to 2016 - Timothy J Albaugh; Thomas R Fox; Rachel L Cook; Jay E Raymond; Rafael A Rubilar; Otávio C Campoe (Forest Science, 2019)

Implications of introgression for wildlife translocations: the case of North American martens - Jocelyn P. Colella; Robert E. Wilson; Sandra L. Talbot; Joseph A. Cook (Conservation Genetics, 2019)

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Using social‐network research to improve outcomes in natural resource management - Julie E. Groce; Megan A. Farrelly; Bradley S. Jorgensen; Carly N. Cook (Conservation Biology, 2019)
The conservation and management of natural resources operates in social–ecological systems in which resource users are embedded in social and environmental contexts that influence their management decisions. Characterizing social networks of resource users can be used to inform understanding of social influences on decision making, and social network analysis (SNA) has emerged as a useful technique to explore these relationships. We synthesized how SNA has been used in 85 studies of natural resource management. We considered how social networks and social processes (e.g., interactions between individuals) influence each other and in turn influence social outcomes (e.g., decisions or actions) that affect environmental outcomes (e.g., improved condition). Descriptive methods were used in 58% of the studies to characterize social processes, and 42% of the studies compared multiple networks or multiple points in time to assess social or environmental outcomes. In 4 studies, authors assessed network interventions intended to affect social processes or environmental outcomes. The heterogeneity in case studies, methods, and analyses preclude general lessons. Thus, to structure and further learning about the role of social networks in achieving environmental outcomes, we created a typology that deconstructs social processes, social outcomes, and environmental outcomes into themes and options of social and ecological measures within each. We suggest shifts in research foci toward intervention studies to aid in understanding causality and inform the design of conservation initiatives. There is a need to develop clearer justification and guidance around the proliferation of network measures. The use of SNA in natural resource management is expanding rapidly; thus, now is the time for the conservation community to build a more rigorous evidence base to demonstrate the extent to which social networks can play a role in achieving desired social and environmental outcomes.

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Restructuring of a mutualism following introduction of Australian fig trees and pollinating wasps to Europe and the USA - E. J. Morgan; T. L. Sutton; C. T. Darwell; J. M. Cook (Biological Invasions, 2018)

Delayed timing of successful spawning of an estuarine dependent fish, black bream Acanthopagrus butcheri - Gregory P. Jenkins; Julia A. Kent; Ryan J. Woodland; Fiona Warry; Stephen E. Swearer; Perran L. M. Cook (Journal of Fish Biology, 2018)
In this paper, we investigate the period of successful spawning for black bream Acanthopagrus butcheri , an obligate estuarine species in southern Australia that typically spawn in spring and early summer. However, back‐calculated spawning dates of juveniles sampled in Gippsland Lakes, Victoria from February to May 2016 indicated that spawning was concentrated over a short period in the Austral mid‐summer (January), with a second spawning in late summer and early autumn (late February–early March). Ichthyoplankton sampling in the tributary estuaries from October to early December collected substantial numbers of fish larvae, dominated by gobiids, eleotrids and retropinnids of freshwater origin, but no A. butcheri . The lack of A. butcheri larvae was consistent with the delayed successful spawning indicated by juvenile otolith data. Freshwater flows declined from late winter to summer, with consistent salinity stratification of the water column. Dissolved oxygen (DO) concentrations were generally very low below the halocline. These conditions may have delayed the upstream spawning migration of adults or may have been unsuitable for survival of eggs and newly‐hatched larvae. Longer‐term predictions for climate change in southern Victoria, including the Gippsland Lakes region, are for lower winter–spring freshwater flows, potentially benefiting the reproductive success of A. butcheri through high water‐column stratification, but only if DO concentrations are not compromised by a lack of high winter flows needed to flush low DO water from the system.

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Vegetation changes in blown-down and scorched forests 10–26 years after the eruption of Mount St. Helens, Washington, USA - James E. Cook; Charles B. Halpern (Plant Ecology, 2018)

Applying the principles of isotope analysis in plant and animal ecology to forensic science in the Americas - Lesley A. Chesson; Janet E. Barnette; Gabriel J. Bowen; J. Renée Brooks; John F. Casale; Thure E. Cerling; Craig S. Cook; Charles B. Douthitt; John D. Howa; Janet M. Hurley; Helen W. Kreuzer; Michael J. Lott; et al. (Oecologia, 2018)

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Impacts of Invasive Phragmites australis on Diamondback Terrapin Nesting in Chesapeake Bay - Cassandra E. Cook; Allison M. McCluskey; Randolph M. Chambers (Estuaries and Coasts, 2018)

Trends of two HPV-associated cancers in Massachusetts: cervical and oropharyngeal cancer - Erin E. Cook; Susan T. Gershman; Jane J. Kim; Rulla M. Tamimi; R. Monina Klevens; Michelle D. Holmes (Cancer Causes & Control, 2018)

Agro-morphological traits of Cicer reticulatum Ladizinsky in comparison to C. echinospermum P.H. Davis in terms of potential to improve cultivated chickpea (C. arietinum L.) - Mirlan Talip; Alper Adak; Abdullah Kahraman; Jens Berger; Duygu Sari; Hatice Sari; R. V. Penmetsa; E. J. von Wettberg; D. R. Cook; Cengiz Toker (Genetic Resources and Crop Evolution, 2018)

Using an in vitro system for maintaining Varroa destructor mites on Apis mellifera pupae as hosts: studies of mite longevity and feeding behavior - Noble I. Egekwu; Francisco Posada; Daniel E. Sonenshine; Steven Cook (Experimental and Applied Acarology, 2018)

Characterization of resistance to the wheat stem sawfly in spring wheat landrace accessions from targeted geographic regions of the world - Andrea C. Varella; David K. Weaver; Jason P. Cook; Nancy K. Blake; Megan L. Hofland; Peggy F. Lamb; Luther E. Talbert (Euphytica, 2017)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Diversification of deermice (Rodentia: genus Peromyscus ) at their north‐western range limit: genetic consequences of refugial and island isolation - Yadéeh E. Sawyer; Melanie J. Flamme; Thomas S. Jung; Stephen O. MacDonald; Joseph A. Cook (Journal of Biogeography, 2017)
Aim We surveyed the genetic variability of deermice (genus Peromyscus ) at the north‐western edge of their range to test for occupancy in multiple, hypothesized ice‐free regions during the late Pleistocene and explore post‐glacial dynamics. Location North‐western North America. Methods We used sequences from four independent nuclear and mitochondrial loci from 341 specimens of Peromyscus maniculatus, Peromyscus keeni and Peromyscus sp. (Yukon) to assess species limits, population structure, and demographical change as a result of historical climate change, using a Bayesian approach. Species distribution models were built in MaxEnt to explore the niche overlap amongst genetically distinct species. Results Divergence amongst three lineages began before the last interglacial, and each shows signs of post‐glacial expansion. Multilocus species trees strongly support P. keeni and Peromyscus sp. (Yukon) as independent from P. maniculatus . Substantial substructure was observed for P. keeni across the fragmented Alexander Archipelago. Northern lineages or clades ( Peromyscus sp. and P. keeni ) differed in potential ecological distributions. Main conclusions At the extreme north‐western range of deermice in North America, three distinct lineages persist reflecting divergence in at least three ice‐free regions [Beringia, Coastal (near Southeast Alaska) and Southern Continental] throughout the latest Pleistocene glacial cycles. Although spatially proximate in Yukon, no locations were identified where these lineages are in contact. Further, west along the Pacific Coast, P. keeni is widespread across the complex landscape of Southeast Alaska, yet there is limited contemporary gene flow amongst island populations, a finding consistent with the barriers produced by rising sea levels at the end of the Last Glacial Maximum.

Temporal abundance and activity trends of vinyl chloride (VC)-degrading bacteria in a dilute VC plume at Naval Air Station Oceana - Yi Liang; Laura J. Cook; Timothy E. Mattes (Environmental Science and Pollution Research, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Environmental predictors of bovine Eimeria infection in western Kenya - D. N. Makau; G. K. Gitau; G. K. Muchemi; L. F. Thomas; E. A. J. Cook; N. A. Wardrop; E. M. Fèvre; W. A. de Glanville (Tropical Animal Health and Production, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Public perception of air pollution and health effects in Nanchang, China - Gui-lian Lan; Zhao-kang Yuan; Jay E. Maddock; Angelie Cook; Yuan-yuan Chu; Bing-bing Pan; Hong Tu; Si Fan; Xiong Liao; Yuanan Lu (Air Quality, Atmosphere & Health, 2016)

Learning from mistakes in climate research - Rasmus E. Benestad; Dana Nuccitelli; Stephan Lewandowsky; Katharine Hayhoe; Hans Olav Hygen; Rob van Dorland; John Cook (Theoretical and Applied Climatology, 2016)

Sedimentological records of the C.E. 1707 Hōei Nankai Trough tsunami in the Bungo Channel, southwestern Japan - Hannah E. Baranes; Jonathan D. Woodruff; Davin J. Wallace; Kinuyo Kanamaru; Timothy L. Cook (Natural Hazards, 2016)

Colistin combination therapy improves microbiologic cure in critically ill patients with multi-drug resistant gram-negative pneumonia - N. L. Parchem; K. A. Bauer; C. H. Cook; J. E. Mangino; C. D. Jones; K. Porter; C. V. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Flood risk management, an approach to managing cross-border hazards - L. J. Bracken; E. A. Oughton; A. Donaldson; B. Cook; J. Forrester; C. Spray; S. Cinderby; D. Passmore; N. Bissett (Natural Hazards, 2016)

A trans‐Atlantic examination of haddock Melanogrammus aeglefinus food habits - J. C. Tam; J. S. Link; S. I. Large; B. Bogstad; A. Bundy; A. M. Cook; G. E. Dingsør; A. V. Dolgov; D. Howell; A. Kempf; J. K. Pinnegar; A. Rindorf; et al. (Journal of Fish Biology, 2016)
The food habits of Melanogrammus aeglefinus were explored and contrasted across multiple north‐eastern and north‐western Atlantic Ocean ecosystems, using databases that span multiple decades. The results show that among all ecosystems, echinoderms are a consistent part of M. aeglefinus diet, but patterns emerge regarding where and when M. aeglefinus primarily eat fishes v . echinoderms. Melanogrammus aeglefinus does not regularly exhibit the increase in piscivory with ontogeny that other gadoids often show, and in several ecosystems there is a lower occurrence of piscivory. There is an apparent inverse relationship between the consumption of fishes and echinoderms in M. aeglefinus over time, where certain years show high levels of one prey item and low levels of the other. This apparent binary choice can be viewed as part of a gradient of prey options, contingent upon a suite of factors external to M. aeglefinus dynamics. The energetic consequences of this prey choice are discussed, noting that in some instances it may not be a choice at all.

Erratum to: Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Sex-specific macronutrient foraging strategies in a highly successful marine predator: the Australasian gannet - Gabriel E. Machovsky-Capuska; Alistair M. Senior; Emily C. Benn; Alice H. Tait; Rob Schuckard; Karen A. Stockin; Willie Cook; Mike Ogle; Katherine Barna; David Melville; Belinda Wright; Cameron Purvin; et al. (Marine Biology, 2016)

Use of an allostatic neurotechnology by adolescents with postural orthostatic tachycardia syndrome (POTS) is associated with improvements in heart rate variability and changes in temporal lobe electrical activity - John E. Fortunato; Catherine L. Tegeler; Lee Gerdes; Sung W. Lee; Nicholas M. Pajewski; Meghan E. Franco; Jared F. Cook; Hossam A. Shaltout; Charles H. Tegeler (Experimental Brain Research, 2016)

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Natural abundance (δ15N) indicates shifts in nitrogen relations of woody taxa along a savanna–woodland continental rainfall gradient - Fiona M. Soper; Anna E. Richards; Ilyas Siddique; Marcos P. M. Aidar; Garry D. Cook; Lindsay B. Hutley; Nicole Robinson; Susanne Schmidt (Oecologia, 2015)

The Smoking Behaviors and Cancer-Related Disparities Among Urban Middle Aged and Older Men Involved in the Criminal Justice System - Pamela Valera; Matthew Anderson; Stephanie H. Cook; Judith Wylie-Rosett; Justin Rucker; Andrea E. Reid (Journal of Cancer Education, 2015)

Reconstruction of the springtime East Asian Subtropical Jet and Western Pacific pattern from a millennial-length Taiwanese tree-ring chronology - W. E. Wright; B. T. Guan; Y.-H. Tseng; E. R. Cook; K.-Y. Wei; S.-T. Chang (Climate Dynamics, 2015)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Global warming and 21st century drying - Benjamin I. Cook; Jason E. Smerdon; Richard Seager; Sloan Coats (Climate Dynamics, 2014)

Temporal ecology in the Anthropocene - E. M. Wolkovich; B. I. Cook; K. K. McLauchlan; T. J. Davies (Ecology Letters, 2014)
Two fundamental axes – space and time – shape ecological systems. Over the last 30 years spatial ecology has developed as an integrative, multidisciplinary science that has improved our understanding of the ecological consequences of habitat fragmentation and loss. We argue that accelerating climate change – the effective manipulation of time by humans – has generated a current need to build an equivalent framework for temporal ecology. Climate change has at once pressed ecologists to understand and predict ecological dynamics in non‐stationary environments, while also challenged fundamental assumptions of many concepts, models and approaches. However, similarities between space and time, especially related issues of scaling, provide an outline for improving ecological models and forecasting of temporal dynamics, while the unique attributes of time, particularly its emphasis on events and its singular direction, highlight where new approaches are needed. We emphasise how a renewed, interdisciplinary focus on time would coalesce related concepts, help develop new theories and methods and guide further data collection. The next challenge will be to unite predictive frameworks from spatial and temporal ecology to build robust forecasts of when and where environmental change will pose the largest threats to species and ecosystems, as well as identifying the best opportunities for conservation.

Reduction of circulating and selective limbic brain levels of (3α,5α)-3-hydroxy-pregnan-20-one (3α,5α-THP) following forced swim stress in C57BL/6J mice - Antoniette M. Maldonado-Devincci; Matthew C. Beattie; Danielle H. Morrow; Raechel E. McKinley; Jason B. Cook; Todd K. O’Buckley; A. Leslie Morrow (Psychopharmacology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Processes and Drivers of Nitrogen Removal in Stormwater Biofiltration - Emily G. I. Payne; Tim D. Fletcher; Perran L. M. Cook; Ana Deletic; Belinda E. Hatt (Critical Reviews in Environmental Science and Technology, 2014)

Foraging behaviour and habitat use of chick-rearing Australasian Gannets in New Zealand - Gabriel E. Machovsky-Capuska; Mark E. Hauber; Mariela Dassis; Eric Libby; Martin C. Wikelski; Rob Schuckard; David S. Melville; Willie Cook; Michelle Houston; David Raubenheimer (Journal of Ornithology, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Turning passive detection systems into field experiments: an application using wetland fishes and enclosures to track fine-scale movement and habitat choice - J. S. Rehage; R. E. Boucek; E. A. Cline; M. I. Cook; R. M. Kobza; A. K. Saha (acta ethologica, 2014)

The number of days on which increment occurs is the primary determinant of annual ring width in Callitris intratropica - David M. Drew; Anna E. Richards; Garry D. Cook; Geoffrey M. Downes; Warwick Gill; Patrick J. Baker (Trees, 2014)

The relationship between glycine transporter 1 occupancy and the effects of the glycine transporter 1 inhibitor RG1678 or ORG25935 on object retrieval performance in scopolamine impaired rhesus monkey - Donnie Eddins; Terence G. Hamill; Vanita Puri; Christopher E. Cannon; Jeffrey A. Vivian; Sandra M. Sanabria-Bohórquez; Jacquelynn J. Cook; John A. Morrow; Fiona Thomson; Jason M. Uslaner (Psychopharmacology, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Effect of the duration of inoculum exposure on development of citrus canker symptoms on seedlings of Swingle citrumelo - Clive H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2014)

Colony social structure in native and invasive populations of the social wasp Vespula pensylvanica - Cause Hanna; Erin D. Cook; Ariel R. Thompson; Lyndzey E. Dare; Amanda L. Palaski; David Foote; Michael A. D. Goodisman (Biological Invasions, 2014)

The ability of people with Parkinson’s disease to modify dual-task performance in response to instructions during simple and complex walking tasks - Valerie E. Kelly; Anne Shumway-Cook (Experimental Brain Research, 2014)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

Arboreal thorn-dwelling ants coexisting on the savannah ant-plant, Vachellia erioloba, use domatia morphology to select nest sites - H. Campbell; M. D. E. Fellowes; J. M. Cook (Insectes Sociaux, 2013)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

Linking anti‐predator behaviour to prey demography reveals limited risk effects of an actively hunting large carnivore - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; Michael D. Jimenez; Rachel C. Cook; John G. Cook; Shannon E. Albeke; Hall Sawyer; P. J. White (Ecology Letters, 2013)
Ecological theory predicts that the diffuse risk cues generated by wide‐ranging, active predators should induce prey behavioural responses but not major, population‐ or community‐level consequences. We evaluated the non‐consumptive effects ( NCE s) of an active predator, the grey wolf ( Canis lupus ), by simultaneously tracking wolves and the behaviour, body fat, and pregnancy of elk ( Cervus elaphus ), their primary prey in the Greater Yellowstone Ecosystem. When wolves approached within 1 km, elk increased their rates of movement, displacement and vigilance. Even in high‐risk areas, however, these encounters occurred only once every 9 days. Ultimately, despite 20‐fold variation in the frequency of encounters between wolves and individual elk, the risk of predation was not associated with elk body fat or pregnancy. Our findings suggest that the ecological consequences of actively hunting large carnivores, such as the wolf, are more likely transmitted by consumptive effects on prey survival than NCE s on prey behaviour.

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Greater impulsivity is associated with decreased brain activation in obese women during a delay discounting task - Luke E. Stoeckel; Donna L. Murdaugh; James E. Cox; Edwin W. Cook; Rosalyn E. Weller (Brain Imaging and Behavior, 2013)

Rejoinder: challenge and opportunity in the study of ungulate migration amid environmental change - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)

Animal migration amid shifting patterns of phenology and predation: lessons from a Yellowstone elk herd - Arthur D. Middleton; Matthew J. Kauffman; Douglas E. McWhirter; John G. Cook; Rachel C. Cook; Abigail A. Nelson; Michael D. Jimenez; Robert W. Klaver (Ecology, 2013)
Migration is a striking behavioral strategy by which many animals enhance resource acquisition while reducing predation risk. Historically, the demographic benefits of such movements made migration common, but in many taxa the phenomenon is considered globally threatened. Here we describe a long‐term decline in the productivity of elk ( Cervus elaphus ) that migrate through intact wilderness areas to protected summer ranges inside Yellowstone National Park, USA. We attribute this decline to a long‐term reduction in the demographic benefits that ungulates typically gain from migration. Among migratory elk, we observed a 21‐year, 70% reduction in recruitment and a 4‐year, 19% depression in their pregnancy rate largely caused by infrequent reproduction of females that were young or lactating. In contrast, among resident elk, we have recently observed increasing recruitment and a high rate of pregnancy. Landscape‐level changes in habitat quality and predation appear to be responsible for the declining productivity of Yellowstone migrants. From 1989 to 2009, migratory elk experienced an increasing rate and shorter duration of green‐up coincident with warmer spring–summer temperatures and reduced spring precipitation, also consistent with observations of an unusually severe drought in the region. Migrants are also now exposed to four times as many grizzly bears ( Ursus arctos ) and wolves ( Canis lupus ) as resident elk. Both of these restored predators consume migratory elk calves at high rates in the Yellowstone wilderness but are maintained at low densities via lethal management and human disturbance in the year‐round habitats of resident elk. Our findings suggest that large‐carnivore recovery and drought, operating simultaneously along an elevation gradient, have disproportionately influenced the demography of migratory elk. Many migratory animals travel large geographic distances between their seasonal ranges. Changes in land use and climate that disparately influence such seasonal ranges may alter the ecological basis of migratory behavior, representing an important challenge for, and a powerful lens into, the ecology and conservation of migratory taxa.

Interspecific effects of 4A-DNT (4-amino-2,6-dinitrotoluene) and RDX (1,3,5-trinitro-1,3,5-triazine) in Japanese quail, Northern bobwhite, and Zebra finch - Michael J. Quinn; Terry L. Hanna; Alicia A. Shiflett; Craig A. McFarland; Michelle E. Cook; Mark S. Johnson; Kurt A. Gust; Edward J. Perkins (Ecotoxicology, 2013)

Amycolatopsis umgeniensis sp. nov., isolated from soil from the banks of the Umgeni River in South Africa - Gareth J. Everest; Marilize le Roes-Hill; Clifford Omorogie; Shuk-Kwan Cheung; Andrew E. Cook; Candice M. Goodwin; Paul R. Meyers (Antonie van Leeuwenhoek, 2013)

Temporal, spatial and ecological dynamics of speciation among amphi‐ B eringian small mammals - Andrew G. Hope; Naoki Takebayashi; Kurt E. Galbreath; Sandra L. Talbot; Joseph A. Cook (Journal of Biogeography, 2013)
Aim Quaternary climate cycles played an important role in promoting diversification across the N orthern H emisphere, although details of the mechanisms driving evolutionary change are still poorly resolved. In a comparative phylogeographical framework, we investigate temporal, spatial and ecological components of evolution within a suite of H olarctic small mammals. We test a hypothesis of simultaneous divergence among multiple taxon pairs, investigating time to coalescence and demographic change for each taxon in response to a combination of climate and geography. Location Beringia, the nexus of the northern continents. Methods We used approximate B ayesian computation methods to test for simultaneous divergence among eight pairs of taxa, using cytochrome b gene sequences. We calculated coalescence times for eastern and western components of each pair and for the combined pairs, and relate dates to Q uaternary climatic periodicity and combinations of environmental events and physical barriers. Population growth and expansion statistics were used to test evolutionary responses among taxa, including range shifts, persistence or periodic extirpation. Species distribution models ( SDM s) for each taxon were used to predict their geographical ranges during the present interglacial, L ast G lacial M aximum and previous interglacial. Results Multiple divergence events across B eringia were primarily coincident with extreme glacial cycles of the late Q uaternary. Structure within B eringia is spatially consistent with at least three environmental barriers arising at different times: the K olyma U plands, B ering S trait and portions of the B ering I sthmus. Levels of divergence varied substantially, indicating evolutionary processes spanning deep and shallow time‐scales. The different demographics among taxa reflect their distinct ecological responses. SDM s predicted regional distributional changes through time and different spatial responses among taxa. Main conclusions Beringia predominantly constituted a dispersal corridor during the early Q uaternary and a major centre of endemism in the late Q uaternary. Coincident with severe glacial cycles, small mammal species were ‘caught’ in B eringia and diversified over multiple climatic phases. Relative genetic differentiation across B eringia appears to be related to ecological differences reflecting a gradual adaptation to B eringian environments through time. Some methodological constraints associated with resolving recent (late Q uaternary) isolation events or drawing inferences from a single locus are discussed.

Epidemiology of Helicobacter pylori infection in six Latin American countries (SWOG Trial S0701) - Carolina Porras; Jesse Nodora; Rachael Sexton; Catterina Ferreccio; Silvia Jimenez; Ricardo L. Dominguez; Paz Cook; Garnet Anderson; Douglas R. Morgan; Laurence H. Baker; E. Robert Greenberg; Rolando Herrero (Cancer Causes & Control, 2013)

Comorbidities and endometrial cancer survival in Hispanics and non-Hispanic whites - Linda S. Cook; Harold E. Nelson; Myles Cockburn; Sara H. Olson; Carolyn Y. Muller; Charles L. Wiggins (Cancer Causes & Control, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

Summary Workshop Report: Facilitating Oral Product Development and Reducing Regulatory Burden Through Novel Approaches to Assess Bioavailability/Bioequivalence - James E. Polli; Jack A. Cook; Barbara M. Davit; Paul A. Dickinson; Domenick Argenti; Nancy Barbour; Alfredo García-Arieta; Jean-Marie Geoffroy; Kerry Hartauer; Shoufeng Li; Amitava Mitra; Francis X. Muller; et al. (The AAPS Journal, 2012)

Holocene climate change and landscape development from a low-Arctic tundra lake in the western Hudson Bay region of Manitoba, Canada - Philip Camill; Charles E. Umbanhowar; Christoph Geiss; William O. Hobbs; Mark B. Edlund; Avery Cook Shinneman; Jeffrey A. Dorale; Jason Lynch (Journal of Paleolimnology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Evaluating the respiratory bioaccessibility of nickel in soil through the use of a simulated lung fluid - Mallory Drysdale; Karin Ljung Bjorklund; Heather E. Jamieson; Philip Weinstein; Angus Cook; Ron T. Watkins (Environmental Geochemistry and Health, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Thoracic Artificial Lung Impedance Studies Using Computational Fluid Dynamics and In Vitro Models - Rebecca E. Schewe; Khalil M. Khanafer; Ryan A. Orizondo; Keith E. Cook (Annals of Biomedical Engineering, 2012)

Macronutrient regulation in the Rasberry crazy ant (Nylanderia sp. nr. pubens) - S. C. Cook; R. A. Wynalda; R. E. Gold; S. T. Behmer (Insectes Sociaux, 2012)

Predicting phenology by integrating ecology, evolution and climate science - Stephanie Pau; Elizabeth M. Wolkovich; Benjamin I. Cook; T. Jonathan Davies; Nathan J. B. Kraft; Kjell Bolmgren; Julio L. Betancourt; Elsa E. Cleland (Global Change Biology, 2011)
Forecasting how species and ecosystems will respond to climate change has been a major aim of ecology in recent years. Much of this research has focused on phenology – the timing of life‐history events. Phenology has well‐demonstrated links to climate, from genetic to landscape scales; yet our ability to explain and predict variation in phenology across species, habitats and time remains poor. Here, we outline how merging approaches from ecology, climate science and evolutionary biology can advance research on phenological responses to climate variability. Using insight into seasonal and interannual climate variability combined with niche theory and community phylogenetics, we develop a predictive approach for species’ reponses to changing climate. Our approach predicts that species occupying higher latitudes or the early growing season should be most sensitive to climate and have the most phylogenetically conserved phenologies. We further predict that temperate species will respond to climate change by shifting in time, while tropical species will respond by shifting space, or by evolving. Although we focus here on plant phenology, our approach is broadly applicable to ecological research of plant responses to climate variability.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

Evaluation of the use of recN sequence analysis in the phylogeny of the genus Amycolatopsis - Gareth J. Everest; Andrew E. Cook; Bronwyn M. Kirby; Paul R. Meyers (Antonie van Leeuwenhoek, 2011)

Proceedings of the “Arthritis, Agriculture, and Rural Life: State of the Art Research, Practices, and Applications” Conference, West Lafayette, Indiana, May 11–13, 2011 - Kathryn E. Cook; William E. Field (Journal of Agromedicine, 2011)

Transcriptome sequencing of an ecologically important graminivorous sawfly: a resource for marker development - N. Cook; N. Aziz; P. E. Hedley; J. Morris; L. Milne; A. J. Karley; S. F. Hubbard; J. R. Russell (Conservation Genetics Resources, 2011)

Transient Supplementation of Anabolic Growth Factors Rapidly Stimulates Matrix Synthesis in Engineered Cartilage - Kenneth W. Ng; Christopher J. O’Conor; Lindsay E. Kugler; James L. Cook; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

A SOAP Web Service for accessing MODIS land product subsets - Suresh K. Santhana Vannan; Robert B. Cook; Jerry Y. Pan; Bruce E. Wilson (Earth Science Informatics, 2011)

Optimal Fire Regimes for Soil Carbon Storage in Tropical Savannas of Northern Australia - Anna E. Richards; Garry D. Cook; Brian T. Lynch (Ecosystems, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

You are what you eat, whenever or wherever you eat it: an integrative analysis of fish food habits in Canadian and U.S.A. waters - A. Bundy; J. S. Link; B. E. Smith; A. M. Cook (Journal of Fish Biology, 2011)
The degree to which fish diet differs by season and area, particularly over broad scales, was examined for the first time in temperate, contiguous north‐west Atlantic Ocean waters by comparing food habit data for 10 species of fishes collected concurrently during the spring and autumn surveys in the U.S.A. (Gulf of Maine proper and Georges Bank) and in the summer survey in Canada (western Scotian Shelf and Bay of Fundy). For most species, there was a general concurrence among the three seasons and four areas: summer diets had the same dominant prey items as spring and autumn diets. Although a suite of multivariate analyses did elucidate some differences in specific proportions of the diet for these species across seasons and areas, the main prey did not substantially change for most of these species. These results suggest that there are (1) minimal differences in diet across season for these species at these taxonomic resolutions, (2) there are minimal differences in diet geographically for these species and (3) differences across species, as expected, are important. Many fisheries ecosystem and multispecies models are dependent on food habit data, where resolving seasonal and spatial differences in diet remains an important consideration; however, the present work implies that amalgamated estimates of diet from seasonal surveys may be a reasonable approach when no finer seasonal resolution exists, as long as due diligence is exercised.

Effects of instructed focus and task difficulty on concurrent walking and cognitive task performance in healthy young adults - Valerie E. Kelly; Alexis A. Janke; Anne Shumway-Cook (Experimental Brain Research, 2010)

Meeting Report: Applied Biopharmaceutics and Quality by Design for Dissolution/Release Specification Setting: Product Quality for Patient Benefit - Arzu Selen; Maria T. Cruañes; Anette Müllertz; Paul A. Dickinson; Jack A. Cook; James E. Polli; Filippos Kesisoglou; John Crison; Kevin C. Johnson; Gordon T. Muirhead; Timothy Schofield; Yi Tsong (The AAPS Journal, 2010)

Wind speed and wind-associated leaf injury affect severity of citrus canker on Swingle citrumelo - C. H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Allelopathy as a mechanism for the invasion of Typha angustifolia - Meghann E. Jarchow; Bradley J. Cook (Plant Ecology, 2009)

The Horsfall-Barratt scale and severity estimates of citrus canker - C. H. Bock; T. R. Gottwald; P. E. Parker; A. Z. Cook; F. Ferrandino; S. Parnell; F. van den Bosch (European Journal of Plant Pathology, 2009)

Physical activity, adiposity, and risk of endometrial cancer - Molly B. Conroy; Jacob R. Sattelmair; Nancy R. Cook; JoAnn E. Manson; Julie E. Buring; I-Min Lee (Cancer Causes & Control, 2009)

Phylogenetic analysis of actinobacterial populations associated with Antarctic Dry Valley mineral soils - Olubukola O. Babalola; Bronwyn M. Kirby; Marilize Le Roes‐Hill; Andrew E. Cook; S. Craig Cary; Stephanie G. Burton; Don A. Cowan (Environmental Microbiology, 2009)
Summary Despite the apparent severity of the environmental conditions in the McMurdo Dry Valleys, Eastern Antarctica, recent phylogenetic studies conducted on mineral soil samples have revealed the presence of a wide diversity of microorganisms, with actinobacteria representing one of the largest phylotypic groups. Previous metagenomic studies have shown that the majority of Antarctic actinobacterial populations are classified as ‘uncultured’. In this study, we assessed the diversity of actinobacteria in Antarctic cold desert soils by complementing traditional culture‐based techniques with a metagenomic study. Phylogenetic analysis of clones generated with actinobacterium‐ and streptomycete‐specific PCR primers revealed that the majority of the phylotypes were most closely related to uncultured Pseudonocardia and Nocardioides species. Phylotypes most closely related to a number of rarer actinobacteria genera, including Geodermatophilus , Modestobacter and Sporichthya , were also identified. While complementary culture‐dependent studies isolated a number of Nocardia and Pseudonocardia species, the majority of the cultured isolates (> 80%) were S treptomyces species – although phylotypes affiliated to the genus Streptomyces were detected at a low frequency in the metagenomic study. This study confirms that Antarctic Dry Valley desert soil harbours highly diverse actinobacterial communities and suggests that many of the phylotypes identified may represent novel, uncultured species.

Is (−)-Catechin a Novel Weapon of Spotted Knapweed (Centaurea stoebe)? - Stephen O. Duke; Amy C. Blair; Franck E. Dayan; Robert D. Johnson; Kumudini M. Meepagala; Daniel Cook; Joanna Bajsa (Journal of Chemical Ecology, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

The thermoinsulation effect of snow cover within a climate model - Benjamin I. Cook; Gordon B. Bonan; Samuel Levis; Howard E. Epstein (Climate Dynamics, 2008)

The Effects of the Herbicide Metolachlor on Agonistic Behavior in the Crayfish, Orconectes rusticus - Michelle E. Cook; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2008)

Summary Workshop Report: Bioequivalence, Biopharmaceutics Classification System, and Beyond - James E. Polli; Bertil S. I. Abrahamsson; Lawrence X. Yu; Gordon L. Amidon; John M. Baldoni; Jack A. Cook; Paul Fackler; Kerry Hartauer; Gordon Johnston; Steve L. Krill; Robert A. Lipper; Waseem A. Malick; et al. (The AAPS Journal, 2008)

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Rapid vegetation responses and feedbacks amplify climate model response to snow cover changes - Benjamin I. Cook; Gordon B. Bonan; Samuel Levis; Howard E. Epstein (Climate Dynamics, 2008)

Len Muscatine (1932–2007) and his contributions to the understanding of algal-invertebrate endosymbiosis - O. Hoegh-Guldberg; G. Muller-Parker; C. B. Cook; R. D. Gates; E. Gladfelter; R. K. Trench; V. M. Weis (Coral Reefs, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Agreement of diagnosis and its date for hematologic malignancies and solid tumors between medicare claims and cancer registry data - Soko Setoguchi; Daniel H. Solomon; Robert J. Glynn; E. Francis Cook; Raisa Levin; Sebastian Schneeweiss (Cancer Causes & Control, 2007)

Alkaloid Profiles, Concentration, and Pools in Velvet Lupine (Lupinus leucophyllus) Over the Growing Season - Stephen T. Lee; Michael H. Ralphs; Kip E. Panter; Daniel Cook; Dale R. Gardner (Journal of Chemical Ecology, 2007)

A multigene analysis of the phylogenetic relationships among the flaviviruses (Family: Flaviviridae) and the evolution of vector transmission - S. Cook; E. C. Holmes (Archives of Virology, 2006)

Bactericidal effects of plasma-generated cluster ions - I. Digel; A. Temiz Artmann; K. Nishikawa; M. Cook; E. Kurulgan; G. M. Artmann (Medical & Biological Engineering & Computing, 2005)

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

The North Atlantic Oscillation and regional phenology prediction over Europe - Benjamin I. Cook; Thomas M. Smith; Michael E. Mann (Global Change Biology, 2005)
We present an integrated modeling study designed to investigate changes in ecosystem level phenology over Europe associated with changes in climate pattern, by the North Atlantic Oscillation (NAO). We derived onset dates from processed NDVI data sets and used growing degree day (GDD) summations from the NCEP re‐analysis to calibrate and validate a phenology model to predict the onset of the growing season over Europe. In a cross‐validation hindcast, the model (PHENOM) is able to explain 63% of the variance in onset date for grid cells containing at least 50% mixed and boreal forest. Using a model developed from previous work we performed climate change scenarios, generating synthetic temperature and GDD distributions under a hypothetically increasing NAO. These new distributions were used to drive PHENOM and project changes in the timing of onset for forested cells over Europe. Results from the climate change scenarios indicate that, if the current trend in the NAO continues, there is the potential for a continued advance to the start of the growing season by as much as 13 days in some areas.

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)

Development of a micro-sward technique for determining intake characteristics of perennial ryegrass varieties - R. J. Orr; K. L. Young; J. E. Cook; R. A. Champion (Euphytica, 2005)

Field-Scale Experiments for Site-Specific Crop Management. Part II: A Geostatistical Analysis - M. J. Pringle; A. B. McBratney; S. E. Cook (Precision Agriculture, 2004)

Field-Scale Experiments for Site-Specific Crop Management. Part I: Design Considerations - M. J. Pringle; S. E. Cook; A. B. McBratney (Precision Agriculture, 2004)

High-quality RNA, cDNA, and derived EST libraries from grapevine (Vitis vinifera L.) - A. B. Iandolino; F. Goes da Silva; H. Lim; H. Choi; L. E. Williams; D. R. Cook (Plant Molecular Biology Reporter, 2004)

Body Mass Index and Risk of Colorectal Cancer in Women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Influence of fluoxetine on positive and negative affect in a clinic-based smoking cessation trial - Jessica Werth Cook; Bonnie Spring; Dennis E. McChargue; Belinda Borrelli; Brian Hitsman; Raymond Niaura; Nancy J. Keuthen; Jean Kristeller (Psychopharmacology, 2004)

AZT inhibits Visna/maedi virus -induced apoptosis - V. Bellet; R. Duval; S. Delebasse; J. Cook-Moreau; C. Bosgiraud (Archives of Virology, 2004)

The severe combined immunodeficient (SCID) mouse model of human immunodeficiency virus encephalitis: Deficits in cognitive function - William C Griffin; Lawrence D Middaugh; Jennifer E Cook; William R Tyor (Journal of NeuroVirology, 2004)

Genetic consequences of Pleistocene glaciations for the tundra vole ( Microtus oeconomus ) in Beringia - Kurt E. Galbreath; Joseph A. Cook (Molecular Ecology, 2004)
Repeated glacial events during the Pleistocene fragmented and displaced populations throughout the northern continents. Different models of the effects of these climate‐driven events predict distinct phylogeographic and population genetic outcomes for high‐latitude faunas. The role of glaciations in (i) promoting intraspecific genetic differentiation and (ii) influencing genetic diversity was tested within a phylogeographic framework using the rodent Microtus oeconomus . The spatial focus for the study was Beringia, which spans eastern Siberia and northwestern North America, and was a continental crossroads and potential high arctic refugium during glaciations. Variation in mitochondrial DNA (cytochrome b and control region; 214 individuals) and nuclear DNA (ALDH1 intron; 63 individuals) was investigated across the Beringian region. Close genetic relationships among populations on either side of the Bering Strait are consistent with a history of periodic land connections between North America and Asia. A genetic discontinuity observed in western Beringia between members of a Central Asian clade and a Beringian clade is geographically congruent with glacial advances and with phylogeographic discontinuities identified in other organisms. Divergent island populations in southern Alaska were probably initially isolated by glacial vicariance, but subsequent differentiation has resulted from insularity. Tests of the genetic effects of postglacial colonization were largely consistent with expansion accompanied by founder effect bottlenecking, which yields reduced diversity in populations from recently deglaciated areas. Evidence that populations in the Beringian clade share a history of expansion from a low‐diversity ancestral population suggests that Beringia was colonized by a small founder population from central Asia, which subsequently expanded in isolation.

The Use of Clinical Trial Simulation to Support Dose Selection: Application to Development of a New Treatment for Chronic Neuropathic Pain - Peter A. Lockwood; Jack A. Cook; Wayne E. Ewy; Jaap W. Mandema (Pharmaceutical Research, 2003)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Uptake of erythromycin by first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), fed live or freeze‐dried enriched adult Artemia or medicated pellets - M A Cook; M B Rust; K Massee; T Majack; M E Peterson (Journal of Fish Diseases, 2003)
The potential to use adult Artemia to deliver erythromycin to first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), was investigated in three trials. In the first trial, first‐feeding sockeye were fed live erythromycin enriched adult Artemia or pellets containing equal amounts of erythromycin for 35 days. At the end of the trial, tissue erythromycin concentration of the fish fed the live Artemia was significantly greater ( P μ g mL −1 ; mean ± SEM), than the tissue concentration of the fish fed the pellets (0.72 ± 0.01 μ g mL −1 ). In the second trial, first‐feeding sockeye were fed either live or freeze‐dried bioencapsulated erythromycin (adult Artemia ) or pellets containing erythromycin daily for 21 days. Mean daily erythromycin concentration in fish fed the freeze‐dried Artemia , live Artemia , or pellets did not differ significantly. In the third trial, apparent erythromycin digestibility was determined. Significantly more ( P Artemia (live or freeze‐dried) appears to be greater than uptake from pellets. Freeze‐dried and live Artemia were equally effective at delivery suggesting enriched freeze‐dried adult Artemia could be produced into a highly palatable, consistent, off‐the‐shelf product.

Holarctic phylogeography of the root vole ( Microtus oeconomus ): implications for late Quaternary biogeography of high latitudes - C. Brunhoff; K. E. Galbreath; V. B. Fedorov; J. A. Cook; M. Jaarola (Molecular Ecology, 2003)
A species‐wide phylogeographical study of the root vole ( Microtus oeconomus ) was performed using the whole 1140 base pair mitochondrial (mt) cytochrome b gene. We examined 83 specimens from 52 localities resulting in 65 unique haplotypes. Our results demonstrate that the root vole is divided into four main mtDNA phylogenetic lineages that seem to have largely allopatric distributions. Net divergence estimates (2.0–3.5%) between phylogroups, as well as relatively high nucleotide diversity estimates within phylogroups, indicate that the distinct phylogeographical structure was initiated by historical events that predated the latest glaciation. European root voles are divided into a Northern and a Central mtDNA phylogroup. The mtDNA data in concert with fossil records imply that root voles remained north of the classical refugial areas in southern Europe during the last glacial period. The currently fragmented populations in central Europe belong to a single mtDNA phylogroup. The Central Asian and the North European lineages are separated by the Ural Mountains, a phylogeographical split also found in collared lemmings ( Dicrostonyx ) and the common vole ( M. arvalis ). The Beringian lineage occurs from eastern Russia through Alaska to northwestern Canada. This distribution is congruent with the traditional boundaries of the Beringian refugium and with phylogeographical work on other organisms. In conclusion, similarities between the phylogeographical patterns in the root vole and other rodents, such as Arctic and subarctic lemmings, as well as more temperate vole species, indicate that late Quaternary geological and climatic events played a strong role in structuring northern biotic communities.

Deep Natural Gas Resources - T. S. Dyman; R. E. Wyman; V. A. Kuuskraa; M. D. Lewan; T. A. Cook (Natural Resources Research, 2003)

Estrogen–progestin replacement therapy and breast cancer risk: the Women's Health Study (United States) - Juliet V. Porch; I-Min Lee; Nancy R. Cook; Kathryn M. Rexrode; Julie E. Buring (Cancer Causes & Control, 2002)

Risk factors for myelodysplastic syndromes: a case–control study in Greece - Maria Dalamaga; Eleni Petridou; Francis E. Cook; Dimitrios Trichopoulos (Cancer Causes & Control, 2002)

The age of fine-root carbon in three forests of the eastern United States measured by radiocarbon - J. Gaudinski; S. Trumbore; E. Davidson; A. Cook; D. Markewitz; D. Richter (Oecologia, 2001)

Stability in the historical pattern of genetic structure of Newfoundland cod (Gadus morhua) despite the catastrophic decline in population size from 1964 to 1994 - Daniel E. Ruzzante; Christopher T. Taggart; Roger W. Doyle; Doug Cook (Conservation Genetics, 2001)

A Riparian Wildlife Habitat Evaluation Scheme Developed Using GIS - DIANE L. SZAFONI; LOUIS R. IVERSON; SHARON E. BAUM; ELIZABETH A. COOK (Environmental Management, 2001)

The climatic response of Phyllocladus aspleniifolius (Labill.) Hook. f in Tasmania - K. J. Allen; E. R. Cook; R. J. Francey; K. Michael (Journal of Biogeography, 2001)
Aim To examine the response of ring widths of Phyllocladus aspleniifolius to maximum and minimum temperatures and to a zonal index (ZI). Location Tasmania, Australia. Methods Between two and four increment cores were obtained from approximately 20 trees at each of 16 sites of P. aspleniifolius across Tasmania. Four regions were defined and temperature data for climate stations from each of these regions were transformed into dimensionless time series appropriate for each region. The ZI was constructed from Melbourne and Hobart mean sea level pressure (MSLP). Correlations were calculated between climate data and ring widths over most of the 20th century. Data were then segregated into two subperiods to assess whether or not temporal changes in ring width response have occurred over the 20th century. Results The dominant feature of the correlation functions was a negative correlation with temperatures of the previous growing season. Correlation between the ZI and ring width is most significant, and positive, in November and March of the previous growing season. Differences in the shape of the correlation functions, and their strength is apparent over the course of the century. In general, correlations have become weaker and less consistent among the 16 sites for the latter part of the century. Temperatures have generally increased during the 1900s over which time period correlations have been calculated. Main conclusions The temporally changing climatic response in ring widths is consistent with a hypothesis of competition for resources between different parts of a plant. A nonlinear response to climate over a short‐time period violates one of the basic assumptions of dendroclimatology, therefore suggesting further investigation of both the physiology of trees used for dendroclimatological purposes and the statistical methods used for climatic reconstruction.

Physical activity and breast cancer risk: the Women's Health Study (United States) - I-Min Lee; Kathryn M. Rexrode; Nancy R. Cook; Charles H. Hennekens; Julie E. Buring (Cancer Causes & Control, 2001)

Molecular analysis of the genotype-phenotype relationship in factor VII deficiency - D. Millar; G. Kemball-Cook; J. McVey; E. Tuddenham; A. Mumford; G. Attock; J. Reverter; N. Lanir; L. Parapia; J. Reynaud; E. Meili; A. von Felton; et al. (Human Genetics, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Trans-Tasman Sea climate variability since ad 1740 inferred from middle to high latitude tree-ring data - R. D'Arrigo; E. Cook; R. Villalba; B. Buckley; J. Salinger; J. Palmer; K. Allen (Climate Dynamics, 2000)

Effects of beta-carotene supplementation on cancer incidence by baseline characteristics in the Physicians' Health Study (United States) - Nancy R. Cook; I-Min Lee; JoAnn E. Manson; Julie E. Buring; Charles H. Hennekens (Cancer Causes & Control, 2000)

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

Bay‐scale population structure in coastal Atlantic cod in Labrador and Newfoundland, Canada - D. E. Ruzzante; J. S. Wroblewski; C. T. Taggart; R. K. Smedbol; D. Cook; S. V. Goddaard (Journal of Fish Biology, 2000)
Polymorphisms at five microsatellite DNA loci provide evidence that Atlantic cod Gadus morhua inhabiting Gilbert Bay, Labrador are genetically distinguishable from offshore cod on the north‐east Newfoundland shelf and from inshore cod in Trinity Bay, Newfoundland. Antifreeze activity in the blood suggests that Gilbert Bay cod overwinter within the Bay. Gilbert Bay cod are also smaller (weight and length) for their age and consequently less fecund for their age, than cod elsewhere within the northern cod complex. The productivity and recruitment potential of coastal cod off Labrador may thus be much lower than that of offshore northern cod or of inshore cod farther south, implying that a more conservative management strategy may be required for cod from coastal Labrador than traditionally practised for northern cod inhabiting less harsh environments. Relatively high F ST and R ST measures of population structure suggest that important barriers to gene flow exist among five components that include two inshore (Gilbert and Trinity Bay) and three offshore cod aggregations on the north‐east Newfoundland Shelf and the Grand Bank. D A and D SW estimates of genetic distance that involve Gilbert Bay cod are approximately three‐ and 10–fold larger, respectively, than estimates not involving Gilbert Bay cod. The differences between inshore cod from Gilbert Bay and Trinity Bay raise the possibility that other genetically distinguishable coastal populations may exist, or may have existed prior to the northern cod fishery collapse. Harvesting strategies for northern cod should recognize the existence of genetic diversity between inshore and offshore components as well as among coastal components.

Hair product use and the risk of breast cancer in young women - Linda S. Cook; Kathleen E. Malone; Janet R. Daling; Lynda F. Voigt; Noel S. Weiss (Cancer Causes & Control, 1999)

Identification of three genes expressed primarily during development in Physarum polycephalum - J. Bailey; L. J. Cook; R. Kilmer-Barber; E. Swanson; L. Solnica-Krezel; K. Lohman; W. F. Dove; J. Dee; R. W. Anderson (Archives of Microbiology, 1999)

The activity of the H + -monocarboxylate cotransporter during pre-implantation development in the mouse - E. A. Harding; M. L. Day; C. A. Gibb; M. H. Johnson; D. I. Cook (Pflügers Archiv - European Journal of Physiology, 1999)

Sex allocation and local mate competition in Old World non-pollinating fig wasps - Mark D. E. Fellowes; Steve G. Compton; James M. Cook (Behavioral Ecology and Sociobiology, 1999)

Nitric oxide donors, sodium nitroprusside and S-nitroso-N-acetylpenicillamine, stimulate myoblast proliferation in vitro - J. A. Ulibarri; P. E. Mozdziak; E. Schultz; C. Cook; T. M. Best (In Vitro Cellular & Developmental Biology - Animal, 1999)

A nuclear DNA basis for shelf‐ and bank‐scale population structure in northwest Atlantic cod ( Gadus morhua ): Labrador to Georges Bank - D. E. RUZZANTE; C. T. TAGGART; D. COOK (Molecular Ecology, 1998)
Variation at five microsatellite DNA loci scored in ≈ 1300 individuals provided evidence of genetic structure among 14 cod ( Gadus morhua ) populations spanning the range of the species in the northwest (NW) Atlantic. Using D A and D SW measures of genetic distance, as well as F ST and R ST measures of population structure, differences are revealed among populations at continental shelf scales (NE Newfoundland Shelf, Grand Banks, Flemish Cap, Scotian Shelf, Georges Bank) where regions are separated by submarine saddles, channels and trenches. However, we also provide evidence of genetic structure at spawning‐bank scales consistent with variation in oceanographic features and in the spatiotemporal distribution of spawning, each of which may represent barriers to gene flow among geographically contiguous populations inhabiting a highly advective environment. The differences described are consistent with postdispersal spawning fidelity to natal areas, a behaviour that may be facilitated by topographically induced gyre‐like circulations that can act as retention mechanisms. Significant degrees of substructure among neighbouring and contiguous cod populations may be most easily explained by the associated oceanographic features and processes that conceivably form the template for the evolution of the structure. We suggest that bathymetric and hydrodynamic structure represents a rational starting point for developing hypotheses to examine the processes that lead to the genetic structuring of marine fish species.

Thermobarometry of the Bleikvassli Zn-Pb-(Cu) deposit, Nordland, Norway - J. L. Rosenberg; P. G. Spry; C. E. Jacobson; N. J. Cook; F. M. Vokes (Mineralium Deposita, 1998)

Multiple independent formations of Tragopogon tetraploids (Asteraceae): evidence from RAPD markers - L. M. COOK; P. S. SOLTIS; S. J. BRUNSFELD; D. E. SOLTIS (Molecular Ecology, 1998)
Polyploidy is widely recognized as a significant force leading to the formation of new plant species. Estimates of the number of angiosperm species with polyploid origins are as high as ≈ 50%; however, in spite of this prevalence, many aspects of polyploid evolution remain poorly understood. Recent studies have suggested that recurrent origins of polyploid species are the rule rather than the exception. The present study is one of only a few designed to quantify the number of independent origins of a polyploid species. The two tetraploid species Tragopogon mirus and T . miscellus (Asteraceae) arose within the past 50 years in the Palouse region of eastern Washington and adjacent northern Idaho. Previous work using morphology, cpDNA and rDNA restriction site analyses, allozymes, cytology, and flavonoid chemistry established that T . mirus had arisen at least five times, and T . miscellus at least twice, on the Palouse. To assess the frequency of multiple origins of these species more rigorously, seven populations of T . mirus and three populations of T . miscellus that were indistinguishable based on previous markers were surveyed using random amplified polymorphic DNA (RAPD) markers; populations of the diploid progenitor species from the same sites were also analysed. Each tetraploid population had a unique RAPD marker profile, suggesting that each population surveyed originated independently of the other populations in the region. Only two of the tetraploid populations combined the RAPD marker profiles of the diploid progenitors occurring at the same site. Both polyploid species, whose ranges and numbers have greatly increased since their formation in the early part of the twentieth century, have formed repeatedly on a local geographical scale and during a short time frame. Furthermore, each tetraploid species is spreading not primarily by dispersal of propagules from a single population of origin, but through repeated, independent polyploidization events that recreate the polyploid taxa.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

The effect of severe eccentric exercise-induced muscle damage on plasma elastase, glutamine and zinc concentrations - M. Gleeson; N. P. Walsh; A. K. Blannin; P. J. Robson; L. Cook; A. E. Donnelly; S. H. Day (European Journal of Applied Physiology, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

Cytokinesis and nodal anatomy in the charophycean green alga Chara zeylanica - M. E. Cook; L. E. Graham; C. A. Lavin (Protoplasma, 1998)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

A CHANGING TEMPERATURE RESPONSE WITH ELEVATION FOR LAGAROSTROBOS FRANKLINII IN TASMANIA, AUSTRALIA - B. M. BUCKLEY; E. R. COOK; M. J. PETERSON; M. BARBETTI (Climatic Change, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Concentrations of Cu, Growth, and Chlorophyll Content of Field-Cultivated Wheat Growing in Naturally Enriched Cu Soil - C. M. Cook; E. Vardaka; T. Lanaras (Bulletin of Environmental Contamination and Toxicology, 1997)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Difference in metabolic profile of potassium canrenoate and spironolactone in the rat: Mutagenic metabolites unique to potassium canrenoate - Chyung S. Cook; Charles L. Hauswald; Grant L. Schoenhard; Charles E. Piper; Arun Patel; Frederick M. Radzialowski; Jeremy D. Hribar; William Aksamit; Pat Finnegan; Roy H. Bible; James A. Oppermann (Archives of Toxicology, 1988)

Detection and prevalence of serotypes of feline syncytial spumaviruses - R. L. P. Flower; G. E. Wilcox; R. D. Cook; T. M. Ellis (Archives of Virology, 1985)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)

Sectional notes - Frank E. Garrett; Roy M. Barnes; W. Frank McGee; A. H. Eddins; W. B. Ward; Verne C. Beverly; H. A. Reiley; Allan W. Purdy; J. C. Campbell; H. J. Evans; Harold Mattson; O. D. Burke; et al. (American Journal of Potato Research, 1947)

The effect of different amounts of spindle tuber and leaf roll on yields of Irish potato - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)

Effect of different amounts of spindle tuber and leaf roll on yields of Irish potatoes - E. L. Leclerg; P. M. Lombard; A. H. Eddins; H. T. Cook; J. C. Campbell (American Journal of Potato Research, 1944)